Biogeochemical markers in juvenile Leach's storm-petrels (Hydrobates leucorhous) stranded offshore are distinct from inshore stranded juveniles and nestlings - Anne N.M.A. Ausems; Sophie Roy; Alexander L. Bond; Laura Crick; Joshua T. Cunningham; April Hedd; Laura A. McFarlane Tranquilla; Jennifer C. Rock; Robert A. Ronconi; Katharine R. Studholme; Christopher R.E. Ward; Sabina I. Wilhelm; et al. (Marine Pollution Bulletin, 2026)

Bioaccumulation of trace elements by Leach's storm-petrels (Hydrobates leucorhous) in the North and South Atlantic Ocean during the non-breeding period - Catherine Potvin; Manon Sorais; Robert A. Ronconi; Katharine R. Studholme; April Hedd; Alexander L. Bond; Vegard S. Bråthen; Sydney M. Collins; Laura Crick; Joshua T. Cunningham; Anne N.M.A. Ausems; David A. Fifield; et al. (Marine Pollution Bulletin, 2026)

Dissolution kinetics of platinum mine by-products for nature-based and engineered carbon dioxide removal - L.A. Bullock; A. Cunningham; J. Matter; D. Hasson; E. Smith; M.T. Duret; E.M. Mervine; R.H. James; D.A.H. Teagle (Applied Geochemistry, 2026)

Wild-harvesting of the fucoid Fucus vesiculosus (Phaeophyceae) at an active oyster aquaculture site - Eoghan Mánus Cunningham; Christine A. Maggs; Pamela J. Walsh (Frontiers in Marine Science, 2026)
Macroalgae are seen as a sustainable resource for industries including agriculture, food, and nutraceuticals. Aquaculture is the dominant form of global seaweed biomass production, yet wild-harvesting remains important in Europe. Fucoid species such as Fucus vesiculosus commonly colonise intertidal shores and artificial structures, including oyster farms in Ireland, where they represent a largely unexploited biomass resource. However, the amount of biomass produced annually on oyster farms is unknown, making it unclear whether this resource could be harvested sustainably and potentially provide a new opportunity for shellfish farmers. Hence, this study investigated the potential for sustainable harvesting by management of F. vesiculosus fouling on an oyster aquaculture site, quantifying post-harvest seaweed biomass yield and regeneration. F. vesiculosus thalli were harvested under three treatments, a control (no cut), a longer cut to ~6 cm (Cut L) and a shorter cut to ~3.5 cm (Cut S) and regrowth was quantified over a 12-month period from April 2025 to 2026. The harvested F. vesiculosus thalli regenerated up to 87% of pre-harvest lengths within 12 months. The thalli showed non-linear seasonal growth patterns, with thallus lengths increasing over time. The Cut S treatment resulted in a higher relative growth rate among treatments and a greater initial biomass yield of 0.54 kg per m of trestle. Having determined the total number of oyster trestles in a 1 km stretch of shoreline, we estimated that ~11 tonnes of biomass could be harvested using the Cut S treatment. Our results suggest that low intensity partial harvesting of settled F. vesiculosus on oyster farms could be sustainable, and our results provide proof-of-concept for future co-location of Fucus crops and oysters within a shellfish aquaculture site.

Exposure to second-generation anticoagulant rodenticides is widespread in the non-target British wild mammals Erinaceus europaeus and Vulpes vulpes - Katharina Seilern-Macpherson; Becki Lawson; Sheonaidh Charman; Stephen Jones; James Rainford; Roy Macarthur; Alexander J. Kent; Andrew A. Cunningham; Libby Barnett (Science of The Total Environment, 2026)

Ion chromatography–ultra-high-resolution mass spectrometry reveals EZH2-driven reprogramming of nucleic acid and protein methylation - Mohamed M.Y. Kaddah; Teresa W-M. Fan; Jahid M.M. Islam; Penghui Lin; Teresa A. Cassel; Richard Cunningham; Tom Brown; Richard M. Higashi; Andrew N. Lane (Analytica Chimica Acta, 2026)

Diabetes Nutrition Education and A Food Security Resource for American Indian and Alaska Native Adults With Type 2 Diabetes: A Pilot and Feasibility Randomized Controlled Trial - Sarah A. Stotz; Luciana Hebert; Kelli Begay; Michelle Dennison; Carmen Byker Shanks; Seth A. Berkowitz; Luohua Jiang; Jessica Lafromboise; Nicholas Begick; Barbara Cunningham; Aisa Trice; Danielle Duran; et al. (Journal of Nutrition Education and Behavior, 2026)

The Sedimentary Geochemistry and Paleoenvironments Project Phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

The Scotland–Canada overturning array (SCOTIA): twenty years of meridional overturning in the subpolar North Atlantic - Alan D. Fox; Neil J. Fraser; Kristin Burmeister; Sam C. Jones; Stuart A. Cunningham; Lewis A. Drysdale; Ahmad Fehmi Dilmahamod; Johannes Karstensen (Ocean Science, 2026)
The Atlantic meridional overturning circulation (AMOC) is expected to decline dramatically over the 21st century, with severe impacts for Northern Hemisphere climate. After 20 years of sustained monitoring in the subtropics, a detectable AMOC weakening trend is now beginning to emerge. However, continuous observations at subpolar latitudes are currently too short-lived to determine any weakening signal above the large-amplitude interannual variability. Here, we introduce a new subpolar observing configuration, SCOTIA (Scotland–Canada overturning array), combining parts of the existing OSNAP mooring array with scattered CTD and Argo data, to extend the record of subpolar AMOC backward in time to cover the subtropical monitoring period, 2004–2024. SCOTIA facilitates a rigorous comparison of the decadal-scale variability in transports and overturning at subpolar and subtropical latitudes. Our results show subpolar AMOC varies on pentadal to decadal timescales with an amplitude comparable to that observed in the subtropics. Anomalously high overturning during 2016–2020 was driven by increased southward transports in the density classes associated with Labrador Sea Water. We find no statistically significant trend in subpolar AMOC during the period 2004–2024.

The behavioural, toxicological, and biochemical effects of caffeine on Lumbriculus variegatus - Grace E. Labdon; Roisin Kelly-Laubscher; Margaret R. Cunningham; Nia A. Davies; Sophie G. Reed; Aidan Seeley (Environmental Toxicology and Pharmacology, 2026)

Behavioural responses to heat in an arid-zone bird vary with thermal, hygric and social factors - J. R. D. Whyte; A. E. McKechnie; J. K. Crossley; S. J. Cunningham (Oecologia, 2026)
The severity of fitness costs resulting from behavioural trade-offs between heat dissipation and activities such as foraging is increasing with advancing climate change. In terrestrial habitats, shade and water may buffer individuals from the negative effects of heat exposure, as may load-lightening in group-living species. We tested the hypothesis that thermal and hygric properties of home ranges (shade and water availability) and social factors (group size) influence the costs associated with hot weather, using a population of white-browed sparrow-weavers ( Plocepasser mahali ) in the southern Kalahari Desert. Across all sparrow-weaver groups, heat avoidance (shade-seeking) and dissipation (panting) behaviours increased with increasing air temperature ( T air ), whereas foraging declined. Birds occupying shadier home ranges delayed the onset of panting to higher T air and foraged less while maintaining overall peck rates. Birds with access to water foraged more, maintained higher peck rates and sought shade at higher T air compared to birds without. However, they did not pant more, making the mechanism underpinning their increased foraging effort unclear. Birds in larger groups both panted more overall and sought shade at lower T air than birds in smaller groups but maintained similar overall peck rates. Taken together, these results suggest birds in shadier home ranges can forage more efficiently, buffering foraging costs at high T air . Our data therefore suggest that some impacts of increasing T air under climate change can be buffered by shade availability, but the impacts of water availability and social factors are less clear.

Drought and reservoir drawdown: implications for bull trout distribution and passage - Blake R. Hamilton; Connor D. Cunningham; Brittany A. Beebe; Craig A. Haskell; Jason G. Romine (Environmental Biology of Fishes, 2026)

The Sedimentary geochemistry and paleoenvironments project phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

Fine-scale biochemical variation in Fucus serratus (Phaeophyceae): Point sampling vs bulk samples and implications for industrial applications - Rebecca E. McKinney; Eoghan Mánus Cunningham; Jack Burton; Stefan Kraan; Jaimie T. A. Dick; Pamela J. Walsh (Journal of Applied Phycology, 2026)
EU policies on nature restoration and sustainability open the door for Fucus cultivation, however, based on the applications of the biomass, industry will have to explicitly account for spatiotemporal fluctuations in biochemical profiles. In general, brown seaweeds show high levels of biochemical variation, adjusting polysaccharide, protein, lipid, and secondary metabolite profiles in response to physiochemical factors and biological interactions, which vary geographically and seasonally. Therefore, in this study we examined the fine-scale spatial variability in two high value components, the total phenolic and protein content of Fucus serratus across three sites in Strangford Lough, Northern Ireland at two timepoints. We assessed how sampling either homogenised bulk or point sampling of thalli could impact detection of variability on an inter- and intra-site scale in August 2024 and February 2025, finding a significant effect on the detection of fine-scale variation in biochemical composition. Homogenised bulk samples were able to display clearer relationships, with February collected samples always possessing a higher protein and phenolic content than August samples. Point sampled thalli displayed high variability, capturing the fine-scale intra-site and intra-specific variation. Homogenisation of biomass delivered a more reliable and reproducible assessment of F. serratus biochemical composition at fine-scale, balancing sensitivity to broad patterns (such as seasonal shifts) with robustness against the high variability observed in single-thallus measurements. Developing this sampling protocol can help deliver actionable, site-scale predictions of yield and metabolite trends, ensuring consistent bioproduct quality.

A decade of continuous Rockall Trough transport observations using moorings and gliders - Kristin Burmeister; Sam C. Jones; Neil J. Fraser; Alan D. Fox; Stuart A. Cunningham; Lewis A. Drysdale; Mark E. Inall; Tiago S. Dotto; N. Penny Holliday (Ocean Science, 2026)
The Rockall Trough, northwest of Scotland and Ireland, is a key conduit for the North Atlantic Current (NAC) and European Slope Current (ESC) transporting heat and salt toward the Nordic Seas and Arctic Ocean while mediating exchanges between the open ocean and the European shelf. We present a decade-long record of Rockall Trough circulation from the Ellett Array providing the first continuous estimates of heat and freshwater transport between 2014 and 2024. We develop a methodology that combines the high spatial resolution of gliders with the high temporal resolution of moorings and ocean reanalysis output producing continuous eastern boundary velocity fields of the ESC for integration into the full Rockall Trough transport product. This approach improves the mean structure of the ESC, capturing the southward undercurrent previously unresolved and enhancing the ability to reproduce extreme, likely mesoscale, transport events. The Rockall Trough transport is dominated by the NAC flowing through the mid basin, exhibiting multi-year variability consistent with changes in the subpolar gyre and the mid-2010s cold freshwater anomaly. The ESC acts as a secondary driver, is not correlated with the NAC and is influenced by along-slope wind stress. Since 2022, warmer and saltier conditions, amplified by the 2023 extreme North Atlantic marine heatwave, have strengthened northward volume, heat, and salt transport through the Ellett Array. Our results highlight the value of sustained glider-based boundary current observations for Atlantic climate monitoring and demonstrate that the combined mooring–glider framework provides a robust and transferable approach for long-term ocean transport monitoring.

Bovine milk glycoproteins concentration influences bacterial growth and anti-pathogenic bioactivities relevant to the infant gut in vitro - Iwona Dziembała-Gładysz; Marie Le Berre; Stephen Cunningham; Laura Walsh; Uthesh Umapathy; Yousef Joubran; Gerard T.A. Fleming; David A. Goulding; Lokesh Joshi; Jonathan O'Regan; Michelle Kilcoyne (International Dairy Journal, 2026)

Carbon dioxide removal during dissolution of granular basalt: A mass balance test of enhanced rock weathering at the hillslope scale - Charles J. Cunningham; Andrew Guertin; Marine Gelin; Louis A. Derry; Hannes H. Bauser; Minseok Kim; Jennifer L. Druhan; Scott Saleska; Peter A. Troch; Jon Chorover (Earth and Planetary Science Letters, 2025)

Population Genomics and the Environmental Drivers of Population Structure in a Cosmopolitan Marine Predator, Tursiops truncatus - Daniel M. Moore; Andre E. Moura; Ada Natoli; Elena Papale; Emily G. Cunningham; Mónica A. Silva; Tilen Genov; Stefania Gaspari; Giuseppa Buscaino; Per Berggren; Darren R. Gröcke; A. Rus Hoelzel (Molecular Ecology, 2025)
The marine environment comprises vast regions without physical barriers to movement, making the understanding of population isolation and the evolution of diversity challenging. This is especially the case for highly mobile marine species. Here we investigate populations of the common bottlenose dolphin ( Tursiops truncatus ) across the Mediterranean Sea and adjacent North Atlantic using high‐resolution genomic markers (RADseq) and stable isotope analyses to better understand the evolution of population structure in this system. High‐resolution genomic data and broad geographic sampling revealed patterns of structure not previously identified, and integration with stable isotope data suggests that prey choice varies across this region. Unexpected patterns included genetic and isotopic similarity between the North Atlantic and the region around Sicily (but not including the medially located Gulf of Cádiz and surrounding regions). The regional habitat within and beyond the Mediterranean Sea is structured with ocean frontal systems including thermal and halocline transitions, several of which show alignment with genetic transitions within our data. Our data help to distinguish among possible drivers of population differentiation for a marine predator that has the potential for long‐distance dispersion.

Ambient compositional heterogeneity of the Pacific upper mantle revealed by the Cretaceous Naifeh-Plumeria seamounts - N.G. Pasqualon; A.J. Pietruszka; V.A. Finlayson; V.D. Wanless; A. Balbas; M.J. Cunningham; J.G. Konter (Earth and Planetary Science Letters, 2025)

Drivers and Dynamics of Salmon Bycatch in the Eastern Bering Sea Pollock Fishery - Lukas B. DeFilippo; Wesley A. Larson; Patrick D. Barry; Curry J. Cunningham; Joseph A. Langan; Sabrina Garcia; Kathrine G. Howard; James N. Ianelli; Diana L. Stram (Fish and Fisheries, 2025)
Minimising bycatch is a pervasive challenge for sustainable fisheries management, the importance of which is amplified for non‐target species or populations that are in decline. In the eastern Bering Sea (EBS) walleye pollock ( Gadus chalcogrammus ) fishery, salmon—most notably Chinook ( Oncorhynchus tshawytscha ) and chum ( O. keta )—are encountered as bycatch. Salmon bycatch in the EBS pollock fishery has become an issue of growing concern, largely due to declines in Western Alaska Chinook and chum salmon, which support directed fisheries vital to the wellbeing of regional communities. Consequently, minimising salmon bycatch is a management priority and requires information on the underlying processes driving encounters between salmon and pollock vessels. In this study, we present a broad synthesis of Chinook and chum salmon bycatch dynamics in the EBS pollock fishery. Applying a hierarchical modelling framework to nearly 120,000 catch records collected over 13 years (2011–2023), we quantify patterns of variation in salmon bycatch over space and time, and environmental drivers thereof. Our results reveal spatially structured, interannual variation in chum and Chinook salmon bycatch associated with oceanographic conditions. We also demonstrate the importance of interactions between bottom depth and local sea surface temperature anomalies in shaping bycatch rates, which vary across fishing seasons and salmon species. By advancing our understanding of the factors that contribute to encounters between pollock vessels and salmon, this study can inform ongoing management efforts aimed at minimising multispecies salmon bycatch in a changing marine ecosystem.

A Review of Methionine and Cysteine: Their Roles as Sinks for Reactive Oxygen and Nitrogen Species, Including Bioinformatic Analysis of Their Percent Compositions in Metabolic Proteins - Bethany F. Laatsch; Burhan A. Ali; Anna R. Berthiaume; Grace C. Cunningham; Sabrina M. Duncan; Nathan Hau; Audrey Ho; Marais A. Loomis; Harrison R. Lowater; Brenya L. McNally; Kate L. Mueller; Matt Poppitz; et al. (Indian Journal of Clinical Biochemistry, 2025)

Design of a vectorized rubidium scalar magnetometer for SmallSat applications - Carolina T. Chism; Robert A. Marshall; Aldo Aguilar-Nadalini; Svenja Knappe; David Malaspina; K. Jeramy Hughes; Michaela Ellmeier; Sebastian Wankmueller; Conor Cunningham; Tyler Maydew; Orang Alem (Advances in Space Research, 2025)

NextGen In A Box (NGIAB): Open-Source containerization of the NextGen framework to enable community-driven hydrology modeling - Arpita Patel; James Halgren; Zach Wills; Nels Frazier; Benjamin Lee; Joshua Cunningham; Jordan Laser; Mohammadsepehr Karimiziarani; Trupesh Patel; Giovanni Romero; Matthew Denno; Sam Lamont; et al. (Environmental Modelling & Software, 2025)

Panmictic Panacea? Demonstrating Good Practices for Developing Spatial Stock Assessments Through Application to Alaska Sablefish ( Anoplopoma fimbria ) - Matthew L. H. Cheng; Craig A. Marsh; Daniel R. Goethel; Peter‐John F. Hulson; Katy Echave; Benjamin C. Williams; Aaron M. Berger; Curry J. Cunningham (Fish and Fisheries, 2025)
Marine species and associated fisheries demonstrate complex spatial dynamics driven by biological, ecosystem and socioeconomic factors and integrating these spatial dynamics into stock assessment models can improve fishery management advice. While preliminary good practices for developing spatial stock assessment models have been proposed, comprehensive demonstrations applying these practices remain limited. Drawing on these good practices, we provide an end‐to‐end demonstration of developing a spatial stock assessment using Alaska sablefish ( Anoplopoma fimbria ). Our demonstration emphasises the utility of high‐resolution data analysis and conceptual models for informing key model structure decisions, the joint development of spatial and spatially‐aggregated models to enhance understanding of population dynamics, and the need for further guidance on integrating tagging data and diagnostic tools in spatial assessments. Spatial models highlighted regional differences in sablefish biomass, recruitment and age structure, but total population estimates generally aligned with outputs from spatially aggregated models. Moreover, the spatial model identified ontogenetic movement patterns for this highly mobile species. Overall, the spatially aggregated model for Alaska sablefish is likely adequate for management advice, but periodic spatial model updates could offer insights into spatial dynamics and regional depletion levels. Thus, we recommend concomitant use of both models: spatially aggregated models for informing population‐wide status, and spatial models for informing spatial fishery dynamics and local depletion. The sablefish application represents one of the first implementations of a spatial stock assessment using recently proposed good practices, serving as a valuable guide for future practitioners by underscoring critical decision points and analyses to address them when developing spatial stock assessments.

Seasonality of meridional overturning in the subpolar North Atlantic: density flux as a metric for understanding the Atlantic meridional overturning circulation - Alan D. Fox; Neil J. Fraser; Stuart A. Cunningham (Ocean Science, 2025)
The Atlantic meridional overturning circulation (AMOC) has a notable seasonal component. This influences the jet stream and the location, frequency, and intensity of extreme weather events. Understanding this seasonality is important for mitigating the impacts of AMOC changes on European weather and climate. Here, we place meridional overturning and fluxes in a coherent framework. This framework highlights the integral relationship between meridional overturning circulation and property transports, both being functions purely of the overturning streamfunction Ψ. Using this framework, we examine the seasonality observed in overturning and density, temperature, and freshwater fluxes at the Overturning in the Subpolar North Atlantic Program (OSNAP) line in the subpolar North Atlantic. We find the seasonal cycle of the MOC metric (the standard measure of overturning, defined as the maximum of the overturning streamfunction) to be dominated by Ekman transports and the large-scale seasonal cycle of surface density; heat flux to be dominated by barotropic velocity variability; the seasonal cycle of freshwater flux to be dominated by a combination of barotropic velocities and the salinity in the western boundary current; and density flux to reflect a broad range of characteristics and processes. We show that the MOC metric is a poor predictor, on seasonal timescales, of either density fluxes or the more societally relevant ocean heat and freshwater transports. This is due to each of these metrics responding to different physical processes. The MOC metric, on seasonal timescales at least, has very high sensitivity to near-surface physical characteristics in a limited geographical area. These characteristics are not necessarily reflective of the fundamental processes driving overturning. Therefore, we suggest caution in the use of the standard MOC metric when studying overturning and the routine use of the density flux as a valuable additional overturning metric.

The psychedelic (−)-2,5-dimethoxy-4-iodoamphetamine [(−)-DOI] demonstrates efficacy in reducing cocaine reward and motivation in male rats - Leah M. Salinsky; Christina R. Merritt; Erik J. Garcia; Robert G. Fox; Joshua C. Zamora; Noelle C. Anastasio; Kathryn A. Cunningham (Psychopharmacology, 2025)
Rationale and objectives Overdose fatalities involving cocaine continue to rise with over 5.3 million cocaine users reported in the United States in 2022. The abuse liability of cocaine is reliant upon inhibition of dopamine ( DA ) reuptake and consequent increase in DA efflux in meso-corticolimbic circuitry that controls reward and motivation. Cocaine also increases serotonin ( 5-HT ) efflux which is integral in cocaine abuse. The 5-HT 2A receptor ( 5-HT 2A R ) is a key regulator of meso-corticolimbic DA release and controls cellular mechanisms underlying cocaine effects. 5-HT 2A R actions contribute importantly to psychedelic mechanisms of action, and the efficacy of these compounds in limiting cocaine intake is unknown. The present studies evaluated the efficacy of acute administration of a psychedelic to reduce cocaine intake using standard and advanced preclinical models of drug self-administration. Methods Both a standard fixed ratio ( FR ) schedule and behavioral economics threshold procedure of cocaine intravenous self-administration were employed to evaluate the efficacy of the psychedelic 5-HT 2A R agonist (−)-2,5-dimethoxy-4-iodoamphetamine [ ( − )-DOI ] to decrease cocaine intake and motivation for cocaine in male rats. The 5-HT 2A R-selective antagonist M100907 was utilized to explore the role of 5-HT 2A R in the effects of (−)-DOI on cocaine intake. Results We found that (−)-DOI dose-dependently reduced intake on the FR5 schedule of cocaine IVSA and left shifted the demand curve to evoke greater sensitivity to price increases in the behavioral economics paradigm. Pretreatment with M100907 abated the efficacy of (−)-DOI on cocaine intake in both paradigms. Conclusion (−)-DOI ‘devalued’ cocaine reward and motivation to take cocaine in a 5-HT 2A R-dependent manner. As serotonergic psychedelics emerge as therapeutic candidates, investigations of 5-HT 2A R-acting psychedelics in preclinical analyses of cocaine intake and relapse vulnerability during abstinence will be valuable as prelude to future clinical trials.

Optimising CFRP strengthening for RC columns subject to axial compression and lateral impact: an experimental study - Abdulrahman A. Almatrafi; Lee S. Cunningham; Zhangjian Wu (Innovative Infrastructure Solutions, 2025)
In a typical frame building, columns can be vulnerable to impact arising from accidental actions such as vehicular collisions. Depending on the nature of the structure and its degree of robustness, failure of a column under impact may lead to progressive collapse. In the case of reinforced concrete (RC) frames, various options exist for strengthening existing columns against impact, including the use of externally bonded carbon fibre reinforced polymer (CFRP). Whilst the application of CFRP in static loading situations has been extensively investigated, comparatively little research has been undertaken on the use of this strengthening method for lateral impact situations. Importantly, for the case of square columns, the effect of the axial loading ratio on the strengthened column’s impact response has not been fully investigated, nor has the identification of optimum CFRP strengthening configurations. The present work details an experimental investigation in which nine RC square columns were tested under lateral impact and co-existing axial compression using a purpose-built test rig incorporating a drop hammer and disc spring pile. Axial compression ratios of 5%, 25% and 50% in relation to the theoretical axial capacity of the column as predicted by Eurocode 2 were investigated. Similarly, a number of practically driven CFRP configurations were examined with a view to the identification of optimum strengthening. The test series revealed the axial compression ratio to be inversely proportional to the lateral displacement resulting from impact. As an alternative to full wrapping of the column member, the use of discrete bands of CFRP was found to produce comparable levels of performance in terms of lateral displacement and crack limitation, whilst resulting in a ~ 40% saving in CFRP material. Both full wrapping and discrete banding achieved at least a 30% reduction in displacement compared to the corresponding un-strengthened member.

A Synthesis of Factors Related to Trends in Abundance and Demography of Alaska Chinook Salmon ( Oncorhynchus tshawytscha , Salmonidae): Implications for Research, Management, and Policy - Chase C. Lamborn; Jan Ohlberger; Timothy E. Walsworth; Peter A. H. Westley; Curry J. Cunningham; Sam Wynsma; Jordan W. Smith (Fish and Fisheries, 2025)
Across Alaska, there have been synchronous declines in the abundance, mean age, and size of Chinook salmon ( Oncorhynchus tshawytscha , Salmonidae), a species with immense social and ecological importance. The decline of Chinook salmon, and regulations addressing declines, have drastically impacted people who rely on Alaska's fisheries. Despite their importance, the drivers causing Chinook salmon declines are still not well understood. Therefore, to improve our understanding of the likely drivers of these large‐scale synchronous declines, we synthesised the peer‐reviewed Chinook salmon literature published between 2010 and 2024 using a weight‐of‐evidence approach. We identified 94 variables used to explain the trends in abundance and demographics of Chinook salmon. Each variable's association with trends in Chinook salmon was individually assessed and integrated using a standardised method. Results of this synthesis suggest the drivers for large‐scale synchronous declines have occurred in the North Pacific Ocean. Specifically, we found marine predation, size selective harvest, and pink salmon ( Oncorhynchus gorbuscha ) abundance are the factors most strongly associated with reduced size and age. Results also suggest ocean productivity–specifically winter sea surface temperature and the North Pacific Gyre Oscillation–are the most frequently identified predictors of regional Chinook salmon abundance. In addition to addressing freshwater factors like adult heat stress and juvenile predation, we suggest research, policy, and management focus on how to better understand and address the interactions between ocean productivity, marine predation, size selective harvest, and pink salmon abundance to improve the condition of Chinook salmon, and the people and ecosystems benefiting from them.

Spatiotemporal drivers of rodenticide exposure in a mammalian forest carnivore - Stephanie A. Cunningham; Jacqueline L. Frair; Paul G. Jensen; Krysten L. Schuler (Science of The Total Environment, 2025)

Large urban trees are keystone structures for Australian microbats - Cara R. Parsons; Maldwyn J. Evans; Darren S. Le Roux; Saul A. Cunningham; Brad Law; Philip Gibbons (Biological Conservation, 2025)

Lifecycle implications and mechanical properties of carbonated biomass ashes as carbon-storing supplementary cementitious materials - Patrick R. Cunningham; Li Wang; Seth Kane; Alyson Kim; Bryan M. Jenkins; Sabbie A. Miller (Biomass and Bioenergy, 2025)

Parasite induced changes in contact behaviour is affected by parasitic status of group members - Alex M. M. Morris; Giles T. Innocent; Emma J. A. Cunningham; Darren P. Croft; Spiridoula Athanasiadou; Michael R. Hutchings; Lesley A. Smith (Behavioral Ecology and Sociobiology, 2025)
Understanding how parasitism may affect social behavior and social networks is key to understanding the impact of infection on a population. Infection can disrupt social networks by altering the behavior of both infected individuals (e.g. by reducing activity) and the behavior of uninfected individuals (e.g. avoiding sick individuals), both of which can have an impact on social group dynamics and parasite transmission. Here we test experimentally how parasitism affects social contact behavior and social network structure using a common parasite infection of sheep. Three treatment groups, each with 4 replicate social groups were established (i) Parasitised; all lambs were infected with a parasitic nematode, (ii) Non-parasitised; all lambs remained uninfected (iii) Mixed; part of each group were infected, and part of the group remained uninfected. Contact behaviours of each individual were recorded using proximity loggers during four phases of infection (pre-parasite, pre-patent, patent-parasite, post-parasite). We found infected individuals in the parasitised and mixed groups reduced contact frequency following infection. Despite the reduction in contacts between infected animals in the mixed group, non-infected individual’s maintained pre-parasite levels of social interactions with their infected conspecifics. These results demonstrate how infection can impact the social behavior of all animals within a group, and how the expression of behavioral change may depend on the parasitic status of all group members and the response of uninfected conspecifics. Significance statement Parasitism is known to influence animal behavior and social interactions; however groups of animals will often contain individuals of different parasitic status. Understanding the behavioral response of both infected and uninfected members of a group is important to predict the consequences of infection throughout a population. We show, under experimental conditions, that parasitism not only reduces the frequency of contacts between infected lambs at the earliest stages of infection in both mixed and single-parasitic state groups, but also the degree of behavior change exhibited by infected animals is influenced by the parasitic status of other individuals within the group. We also show that although infected animals in mixed-state groups had reduced contact frequency with their infected groupmates, non-infected animal’s maintained pre-infection levels of social interactions.

Quantifying taxon-specific habitat connectivity requirements of urban wildlife using structured expert judgement - Stephanie K. Courtney Jones; Luke S. O'Loughlin; Danswell Starrs; Jacinta E. Humphrey; Stephanie A. Pulsford; Hugh Allan; Matt Beitzel; Kym Birgen; Suzi Bond; Jenny Bounds; Deborah Bower; Renee Brawata; et al. (Biological Conservation, 2025)

Forecasting drought using machine learning: a systematic literature review - Ricardo S. Oyarzabal; Leonardo B. L. Santos; Christopher Cunningham; Elisangela Broedel; Glauston R. T. de Lima; Gisleine Cunha-Zeri; Jerusa S. Peixoto; Juliana A. Anochi; Klaifer Garcia; Lidiane C. O. Costa; Luana A. Pampuch; Luz Adriana Cuartas; et al. (Natural Hazards, 2025)

Connectivity Benefits Most Woodland Invertebrate Species but Only in Landscapes With Low Woodland Cover - Charles A. Cunningham; Colin M. Beale; Diana E. Bowler; Michael J. O. Pocock; Robin Hutchinson; Piran C. L. White; Merryn Hunt; Lindsay Maskell; Jane K. Hill (Ecology Letters, 2025)
Connectivity is widely assumed to benefit biodiversity, but this has not been extensively quantified across multiple taxa and landscapes. Focusing on the UK, where woodland cover is low (13%), we analysed species occurrence records from citizen science for over 800 broadleaf woodland‐associated invertebrate species from 15 taxonomic groups in relation to woodland cover and connectivity. Overall, increased woodland connectivity positively affects broadleaf‐associated species occurrence (effect of connectivity across species, accounting for positive effect of broadleaf cover). The benefits of connectivity varied considerably by species: 39% of species showed a significant positive effect, while for 3% it was significantly negative. However, the interaction between cover and connectivity revealed that, overall, connectivity benefits are only found in low cover landscapes. Our findings emphasise potential biodiversity benefits from maximising connectivity when increasing woodland cover and highlight the importance of spatial targeting in restoration efforts, especially in landscapes with low woodland cover.

Ranavirus in native amphibians from the Pyrenees National Park, France: a case study - Alexandra Peñafiel-Ricaurte; Stephen J. Price; Matthew C. Fisher; Jaime Bosch; Andrew A. Cunningham; Claudio Azat (European Journal of Wildlife Research, 2025)

Compressive strength and regional supply implications of rice straw and rice hull ashes used as supplementary cementitious materials - Patrick R. Cunningham; Li Wang; Somayeh Nassiri; Peter Thy; John T. Harvey; Bryan M. Jenkins; Sabbie A. Miller (Resources, Conservation and Recycling, 2025)

Test of Rapamycin in Aging Dogs (TRIAD): study design and rationale for a prospective, parallel-group, double-masked, randomized, placebo-controlled, multicenter trial of rapamycin in healthy middle-aged dogs from the Dog Aging Project - Amanda E. Coleman; Kate E. Creevy; Rozalyn Anderson; May J. Reed; Virginia R. Fajt; Kathleen M. Aicher; Genna Atiee; Brian G. Barnett; Ryan D. Baumwart; Beth Boudreau; Suzanne M. Cunningham; Matthew D. Dunbar; et al. (GeroScience, 2025)

Inpatient referrals to a specialist falls and syncope service: prevalence of STOPPFall FRIDs and review of deprescribing patterns - D. O’Donnell; T. Zainal; K. Malomo; N. Fitzpatrick; C. Rice; L. Byrne; R. Briggs; C. Cunningham; R. A. Kenny; A. H. Lavan (European Journal of Clinical Pharmacology, 2025)

A Conceptual Framework for Measuring Ecological Novelty - Timothy L. Staples; Jessica Blois; Katie L. Cramer; Emer T. Cunningham; Maria Dornelas; Simon G. Haberle; Tina Heger; Wolfgang Kiessling; Anne E. Magurran; Aaron O'Dea; Amelia M. Penny; Volker C. Radeloff; et al. (Global Ecology and Biogeography, 2025)
Background Human pressures are driving the emergence of unprecedented, ‘novel’, ecological and environmental systems. The concept of novel (eco)systems is well accepted by the scientific community, but the use and measurement of novelty has outgrown initial definitions and critiques. There are still unresolved methodological and conceptual differences in quantifying novelty that prevent a unified research approach. Framework Here we present a conceptual framework and guidelines to unify past and future measurement of ecological novelty. Under this framework, novelty is a property of an ecological or environmental entity of interest. Novelty is quantified as the comparison between the target entity and a reference set, measured as the summary of degrees of difference across one or more dimensions. Choices in these components, particularly the reference set, can change resulting novelty measurements and inferences. Showcase We provide a case‐study to showcase our framework, measuring pre‐ and post‐European novelty in 99 pollen assemblages in Midwest USA forests. We paired this quantitative exploration with a five‐step process designed to improve the utility and outcomes of novelty analyses. Conclusions Quantitative novelty has immense value in studies of abrupt ecological change, linking climatic and ecological change, biotic interactions and invasions, species range shifts and fundamental theories. Our framework offers a unified overview and is also primed for integration into management and restoration workflows, providing consistent and robust measurements of novelty to support decision making, priority setting and resource allocation.

An interdisciplinary approach to improving conservation outcomes for parasites - Timothy M. Brown; Alison M. Dunn; Rupert J. Quinnell; Ellen Clarke; Andrew A. Cunningham; Simon J. Goodman (Conservation Biology, 2025)
Parasites represent a significant proportion of Earth's biodiversity and play important roles in the ecology and biology of ecosystems and hosts, making them an important target for conservation. Despite increasing calls to prioritize protection for parasites in the academic literature, they remain undervalued and underrepresented in global biodiversity conservation efforts, not least due to the perception that the interests of parasite and host conservation are opposing and the common misconception that parasites are a threat, rather than a benefit, to conservation. We considered whether taking an interdisciplinary approach to parasite conservation research will generate novel insights and solutions concerning why and how parasite conservation should be practiced for the benefit of parasites, their hosts, ecosystems, and people. We argue that 2 of the main barriers to more widespread parasite conservation are the knowledge gap concerning the role of sociocultural factors affecting the willingness to enact parasite conservation and the lack of a consistent and cohesive philosophical basis for parasite conservation. Possible sociocultural barriers to parasite conservation include misconceptions of the risks posed by parasites, taxonomic bias, differences in conservation values, economic constraints, and technical challenges. The use of social science can generate insights into levels of awareness and support for parasite conservation and improve understanding of how human values and attitudes mediate conservation practices concerning parasites. Such knowledge will have a critical role in addressing sociocultural barriers and improving support for parasite conservation. Issues with the current philosophical basis for parasite conservation include contradictory accounts of which parasites merit conservation, insufficient explanation of how different conservation values apply to parasite biodiversity, and the existence of a false antagonism between host and parasite conservation. Greater engagement with philosophical work on environmental ethics and biological unitization will strengthen existing arguments for parasite conservation and will support conservation decision‐making processes.

Land Use Change Consistently Reduces α‐ But Not β‐ and γ‐Diversity of Bees - Toby P. N. Tsang; A. A. Amado De Santis; Gabriela Armas‐Quiñonez; John S. Ascher; Eva Samanta Ávila‐Gómez; András Báldi; Kimberly M. Ballare; Mario V. Balzan; Weronika Banaszak‐Cibicka; Svenja Bänsch; Yves Basset; Adam J. Bates; et al. (Global Change Biology, 2025)
Land use change threatens global biodiversity and compromises ecosystem functions, including pollination and food production. Reduced taxonomic α‐diversity is often reported under land use change, yet the impacts could be different at larger spatial scales (i.e., γ‐diversity), either due to reduced β‐diversity amplifying diversity loss or increased β‐diversity dampening diversity loss. Additionally, studies often focus on taxonomic diversity, while other important biodiversity components, including phylogenetic diversity, can exhibit differential responses. Here, we evaluated how agricultural and urban land use alters the taxonomic and phylogenetic α‐, β‐, and γ‐diversity of an important pollinator taxon—bees. Using a multicontinental dataset of 3117 bee assemblages from 157 studies, we found that taxonomic α‐diversity was reduced by 16%–18% in both agricultural and urban habitats relative to natural habitats. Phylogenetic α‐diversity was decreased by 11%–12% in agricultural and urban habitats. Compared with natural habitats, taxonomic and phylogenetic β‐diversity increased by 11% and 6% in urban habitats, respectively, but exhibited no systematic change in agricultural habitats. We detected a 22% decline in taxonomic γ‐diversity and a 17% decline in phylogenetic γ‐diversity in agricultural habitats, but γ‐diversity of urban habitats was not significantly different from natural habitats. These findings highlight the threat of agricultural expansions to large‐scale bee diversity due to systematic γ‐diversity decline. In addition, while both urbanization and agriculture lead to consistent declines in α‐diversity, their impacts on β‐ or γ‐diversity vary, highlighting the need to study the effects of land use change at multiple scales.

Community-level responses and environmental fate of metformin in freshwater mesocosms - Nicholas C. Blandford; Vince Palace; José Luis Rodríguez-Gil; Lauren Timlick; Madeline Stanley; Richard A. Frank; Sheena Campbell; Martina Rudy; Stephanie Marshall; Abby Wynia; Thomas Clark; Jessie Cunningham; et al. (Science of The Total Environment, 2024)

Stable silicon isotope fractionation reflects the routing of water through a mesoscale hillslope - Andrew Guertin; Charlie Cunningham; Julien Bouchez; Marine Gelin; Jon Chorover; Hannes Bauser; Minseok Kim; Peter Troch; Louis A. Derry; Jennifer L. Druhan (Earth and Planetary Science Letters, 2024)

Identification of novel microcystins in algal extracts by a liquid chromatography–high-resolution mass spectrometry data analysis pipeline - Kirsten A. Cottrill; Christopher O. Miles; Logan C. Krajewski; Brady R. Cunningham; William Bragg; Noelani R. Boise; Kristin D. Victry; David S. Wunschel; Karen L. Wahl; Elizabeth I. Hamelin (Harmful Algae, 2024)

Free radical copolymerization kinetics of bio-based dibutyl itaconate and n-butyl acrylate - Tomaž Pirman; Connor A. Sanders; Martin Ocepek; Michael F. Cunningham; Blaž Likozar; Robin A. Hutchinson (Chemical Engineering Journal, 2024)

The BirdLife Seabird Tracking Database: 20 years of collaboration for marine conservation - Ana P.B. Carneiro; Maria P. Dias; Bethany L. Clark; Elizabeth J. Pearmain; Jonathan Handley; Amy R. Hodgson; John P. Croxall; Richard A. Phillips; Steffen Oppel; Joanne M. Morten; Ben Lascelles; Cleo Cunningham; et al. (Biological Conservation, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Body size and early marine conditions drive changes in Chinook salmon productivity across northern latitude ecosystems - Megan L. Feddern; Rebecca Shaftel; Erik R. Schoen; Curry J. Cunningham; Brendan M. Connors; Benjamin A. Staton; Al von Finster; Zachary Liller; Vanessa R. von Biela; Katherine G. Howard (Global Change Biology, 2024)
Disentangling the influences of climate change from other stressors affecting the population dynamics of aquatic species is particularly pressing for northern latitude ecosystems, where climate‐driven warming is occurring faster than the global average. Chinook salmon ( Oncorhynchus tshawytscha ) in the Yukon‐Kuskokwim (YK) region occupy the northern extent of their species' range and are experiencing prolonged declines in abundance resulting in fisheries closures and impacts to the well‐being of Indigenous people and local communities. These declines have been associated with physical (e.g., temperature, streamflow) and biological (e.g., body size, competition) conditions, but uncertainty remains about the relative influence of these drivers on productivity across populations and how salmon–environment relationships vary across watersheds. To fill these knowledge gaps, we estimated the effects of marine and freshwater environmental indicators, body size, and indices of competition, on the productivity (adult returns‐per‐spawner) of 26 Chinook salmon populations in the YK region using a Bayesian hierarchical stock‐recruitment model. Across most populations, productivity declined with smaller spawner body size and sea surface temperatures that were colder in the winter and warmer in the summer during the first year at sea. Decreased productivity was also associated with above average fall maximum daily streamflow, increased sea ice cover prior to juvenile outmigration, and abundance of marine competitors, but the strength of these effects varied among populations. Maximum daily stream temperature during spawning migration had a nonlinear relationship with productivity, with reduced productivity in years when temperatures exceeded thresholds in main stem rivers. These results demonstrate for the first time that well‐documented declines in body size of YK Chinook salmon were associated with declining population productivity, while taking climate into account.

Opening the black box: New insights into the role of temperature in the marine distributions of Pacific salmon - Joseph A. Langan; Curry J. Cunningham; Jordan T. Watson; Skip McKinnell (Fish and Fisheries, 2024)
Pacific salmon ( Oncorhynchus spp.) spend much of their life near the ocean surface where climatic and oceanographic conditions affect their habitat and survival. Despite decades of study, critical knowledge gaps persist regarding their ecology and distributions. Consequently, it has been difficult to assess how environmental conditions influence the high‐seas distribution and habitat use of these culturally and socioeconomically important fishes, presenting challenges to fisheries managers trying to evaluate how climate change and fishing activities may impact salmon populations. We used a recently compiled, comprehensive database of historical coastal and high‐seas salmon survey data (1953–2022) in the North Pacific to fit species distribution models that (1) characterize the marine spatial distribution of six species of Oncorhynchus , (2) evaluate species‐specific temperature preferences, and (3) investigate how species' temperature preferences influence distribution. Sea surface temperature, along with seasonal migrations associated with spawning and feeding, significantly affects the distribution of all species, where the warm limits of estimated preferred thermal ranges were more similar than the cold limits. Furthermore, the distributions of some species appear more responsive to temperature than others and recently observed warm conditions have likely impacted realized ranges. These models have expanded our understanding of salmon ocean distributions and thermal niches by providing a unique window into this often unobserved but important part of the life cycle. They also serve as a baseline for future investigations into the mechanisms influencing salmon spatial ecology, responses to climate change, and vulnerability to harvest across the North Pacific.

Where the rubber meets the road: Emerging environmental impacts of tire wear particles and their chemical cocktails - Paul M. Mayer; Kelly D. Moran; Ezra L. Miller; Susanne M. Brander; Stacey Harper; Manuel Garcia-Jaramillo; Victor Carrasco-Navarro; Kay T. Ho; Robert M. Burgess; Leah M. Thornton Hampton; Elise F. Granek; Margaret McCauley; et al. (Science of The Total Environment, 2024)

Pacific salmon in the Canadian Arctic highlight a range‐expansion pathway for sub‐Arctic fishes - Karen M. Dunmall; Joseph A. Langan; Curry J. Cunningham; James D. Reist; Humfrey Melling (Global Change Biology, 2024)
Rapid climate change is altering Arctic ecosystems at unprecedented rates. These changes in the physical environment may open new corridors for species range expansions, with substantial implications for subsistence‐dependent communities and sensitive ecosystems. Over the past 20 years, rising incidental harvest of Pacific salmon by subsistence fishers has been monitored across a widening range spanning multiple land claim jurisdictions in Arctic Canada. In this study, we connect Indigenous and scientific knowledges to explore potential oceanographic mechanisms facilitating this ongoing northward expansion of Pacific salmon into the western Canadian Arctic. A regression analysis was used to reveal and characterize a two‐part mechanism related to thermal and sea‐ice conditions in the Chukchi and Beaufort seas that explains nearly all of the variation in the relative abundance of salmon observed within this region. The results indicate that warmer late‐spring temperatures in a Chukchi Sea watch‐zone and persistent, suitable summer thermal conditions in a Beaufort Sea watch‐zone together create a range‐expansion corridor and are associated with higher salmon occurrences in subsistence harvests. Furthermore, there is a body of knowledge to suggest that these conditions, and consequently the presence and abundance of Pacific salmon, will become more persistent in the coming decades. Our collaborative approach positions us to document, explore, and explain mechanisms driving changes in fish biodiversity that have the potential to, or are already affecting, Indigenous rights‐holders in a rapidly warming Arctic.

Predicting energy consumption of zero emission buses using route feature selection methods - L.A.W. Blades; T. Matthews; T.E. McGrath; J. Early; G. Cunningham; A. Harris (Transportation Research Part D: Transport and Environment, 2024)

First report of Ornithogalum virus 3 in Galtonia candicans in the United Kingdom - J Dixon; K Chisnall; M Mynett; C Cunningham; G Webster; A Skelton; A. R. Fowkes; A Fox (Journal of Plant Pathology, 2023)

Revising vulnerability assessments of montane birds in the colombian páramo to account for threats from climate change - Christopher J Wheatley; Colin M Beale; Piran C L White; Adrián Villaseñor; Adriana Sanchez; Charles A Cunningham; Jane K Hill (Biodiversity and Conservation, 2023)
Tropical montane ecosystems are highly vulnerable to global climate change, but their species-level conservation vulnerability assessments generally do not incorporate climate threats. The Colombian páramo is a highly diverse montane ecosystem but it contains relatively few species currently identified as threatened on the IUCN Red List. We explore whether current assessments need revising to account for climate change threats for páramo species. We use a climate change vulnerability assessment framework to evaluate the risks and opportunities from climate change for 60 bird species within the Colombian páramo. We explore two potential climate change scenarios (RCP 2.6 and RCP 8.5), representing best and worst-case projections. We find that more than half (52–68%, depending on the scenario) of bird species will be threatened by climate change by the end of the century, but a very poor agreement between the current conservation status of species and their climate vulnerability score. We find ~ 90% of species identified as climate-threatened are not currently identified as being of conservation concern, representing a substantial new suite of priority species within the Colombian páramo. Overall, we identify up to 34 páramo bird species that are threatened by climate change but not currently listed as being of conservation concern. Similar mismatches may also occur in other montane taxa and so updating species risk assessments to account for climate change is urgently needed. Implementation of appropriate conservation actions is also needed to reduce species’ risks from climate change.

A zero-dose vulnerability index for equity assessment and spatial prioritization in low- and middle-income countries - C.E. Utazi; H.M.T. Chan; I. Olowe; A. Wigley; N. Tejedor-Garavito; A. Cunningham; M. Bondarenko; J. Lorin; D. Boyda; D. Hogan; A.J. Tatem (Spatial Statistics, 2023)

A novel climate and health decision support platform: Approach, outputs, and policy considerations - Jeremy J. Hess; Timothy J. Sheehan; Alyssa Miller; Rad Cunningham; Nicole A. Errett; Tania Busch Isaksen; Jason Vogel; Kristie L. Ebi (Environmental Research, 2023)

Factors influencing mercury exposure in Arctic-breeding shorebirds - Marie Perkins; Iain J. Stenhouse; Richard B. Lanctot; Stephen Brown; Joël Bêty; Megan Boldenow; Jenny Cunningham; Willow English; River Gates; H. Grant Gilchrist; Marie-Andrée Giroux; Kirsten Grond; et al. (Ecotoxicology, 2023)

Intersex manifestation in the rainbow darter (Etheostoma caeruleum): Are adult male fish susceptible to developing and recovering from intersex after exposure to endocrine active compounds? - Keegan A. Hicks; Meghan L.M. Fuzzen; Hadi A. Dhiyebi; Leslie M. Bragg; Patricija Marjan; Jessie Cunningham; Mark E. McMaster; Nivetha Srikanthan; Kirsten E. Nikel; Maricor J. Arlos; Mark R. Servos (Aquatic Toxicology, 2023)

Local tastes and global flavors: food choice in the context of the nutrition transition in South India - Asha Nadabar; Shailaja S. Patil; Ashlesha Datar; Rebecca Jones-Antwi; Solveig A. Cunningham (Food Security, 2023)

Tidal to decadal scale hydrodynamics at two contrasting cold-water coral sites in the Northeast Atlantic - Christian Mohn; Jørgen L.S. Hansen; Marina Carreiro-Silva; Stuart A. Cunningham; Evert de Froe; Carlos Dominguez-Carrió; Stefan Gary; Ronnie N. Glud; Cordula Göke; Clare Johnson; Telmo Morato; Eva Friis Møller; et al. (Progress in Oceanography, 2023)

The role of Dnmt1 in oocyte development - Emily A. Shelby; Elizabeth C. McKinney; Christopher B. Cunningham; Alvin M. Simmons; Allen J. Moore; Patricia J. Moore (Journal of Insect Physiology, 2023)

Autotrophic denitrification supported by sphalerite and oyster shells: Chemical and microbiome analysis - Erica A. Dasi; Jeffrey A. Cunningham; Emmanuel Talla; Sarina J. Ergas (Bioresource Technology, 2023)

Climate change–induced immigration to the United States has mixed influences on public support for climate change and migrants - Ash Gillis; Nathaniel Geiger; Kaitlin Raimi; Julia Lee Cunningham; Melanie A. Sarge (Climatic Change, 2023)

Research needs, environmental concerns, and logistical considerations for incorporating livestock grazing into coastal upland habitat management - K. Gill; K.A. Chenier; A. Free; J. Goff; J.L. Pitchford; K. Cressman; M. Posten; E. Brunden; M. Shelton; K. Swanson; S.R. Cunningham; J. Garland; et al. (Journal of Environmental Management, 2023)

Observation-based estimates of volume, heat, and freshwater exchanges between the subpolar North Atlantic interior, its boundary currents, and the atmosphere - Sam C. Jones; Neil J. Fraser; Stuart A. Cunningham; Alan D. Fox; Mark E. Inall (Ocean Science, 2023)
The Atlantic Meridional Overturning Circulation (AMOC) transports heat and salt between the tropical Atlantic and Arctic oceans. The interior of the North Atlantic subpolar gyre (SPG) is responsible for the much of the water mass transformation in the AMOC, and the export of this water to intensified boundary currents is crucial for projecting air–sea interaction onto the strength of the AMOC. However, the magnitude and location of exchange between the SPG and the boundary remains unclear. We present a novel climatology of the SPG boundary using quality-controlled CTD (conductivity–temperature–depth) and Argo hydrography, defining the SPG interior as the oceanic region bounded by 47∘ N and the 1000 m isobath. From this hydrography we find geostrophic flow out of the SPG around much of the boundary with minimal seasonality. The horizontal density gradient is reversed around western Greenland, where the geostrophic flow is into the SPG. Surface Ekman forcing drives net flow out of the SPG in all seasons with pronounced seasonality, varying between 2.45 ± 0.73 Sv in the summer and 7.70 ± 2.90 Sv in the winter. We estimate heat advected into the SPG to be between 0.14 ± 0.05 PW in the winter and 0.23 ± 0.05 PW in the spring, and freshwater advected out of the SPG to be between 0.07 ± 0.02 Sv in the summer and 0.15 ± 0.02 Sv in the autumn. These estimates approximately balance the surface heat and freshwater fluxes over the SPG domain. Overturning in the SPG varies seasonally, with a minimum of 6.20 ± 1.40 Sv in the autumn and a maximum of 10.17 ± 1.91 Sv in the spring, with surface Ekman the most likely mediator of this variability. The density of maximum overturning is at 27.30 kg m−3, with a second, smaller maximum at 27.54 kg m−3. Upper waters (σ0 27.54 kg m−3) exiting to the south. Our results support the present consensus that the formation and pre-conditioning of Subpolar Mode Water in the north-eastern Atlantic is a key determinant of AMOC strength.

Wild fish responses to wastewater treatment plant upgrades in the Grand River, Ontario - Kirsten E. Nikel; Gerald R. Tetreault; Patricija Marjan; Keegan A. Hicks; Meghan L.M. Fuzzen; Nivetha Srikanthan; Emily K. McCann; Hadi Dhiyebi; Leslie M. Bragg; Pam Law; Dominika Celmer-Repin; Sonya Kleywegt; et al. (Aquatic Toxicology, 2023)

Time-varying effects of local weather on behavior and probability of breeding deferral in two Arctic-nesting goose populations - Stephanie A. Cunningham; Toryn L. J. Schafer; Christopher K. Wikle; Jay A. VonBank; Bart M. Ballard; Lei Cao; Stuart Bearhop; Anthony D. Fox; Geoff M. Hilton; Alyn J. Walsh; Larry R. Griffin; Mitch D. Weegman (Oecologia, 2023)
Arctic-nesting geese face energetic challenges during spring migration, including ecological barriers and weather conditions (e.g., precipitation and temperature), which in long-lived species can lead to a trade-off to defer reproduction in favor of greater survival. We used GPS location and acceleration data collected from 35 greater white-fronted geese of the North American midcontinent and Greenland populations at spring migration stopovers, and novel applications of Bayesian dynamic linear models to test daily effects of minimum temperature and precipitation on energy expenditure (i.e., overall dynamic body acceleration, ODBA) and proportion of time spent feeding (PTF), then examined the daily and additive importance of ODBA and PTF on probability of breeding deferral using stochastic antecedent models. We expected distinct responses in behavior and probability of breeding deferral between and within populations due to differences in stopover area availability. Time-varying coefficients of weather conditions were variable between ODBA and PTF, and often did not show consistent patterns among birds, indicating plasticity in how individuals respond to conditions. An increase in antecedent ODBA was associated with a slightly increased probability of deferral in midcontinent geese but not Greenland geese. Probability of deferral decreased with increased PTF in both populations. We did not detect any differentially important time periods. These results suggest either that movements and behavior throughout spring migration do not explain breeding deferral or that ecological linkages between bird decisions during spring and subsequent breeding deferral were different between populations and across migration but occurred at different time scales than those we examined.

Incubation scheduling by African Black Oystercatchers: effects of weather, tide phase, and time of day - Bukola D. A. Braimoh-Azaki; Susan J. Cunningham; Will Cresswell (Journal of Ornithology, 2023)

Exceptional freshening and cooling in the eastern subpolar North Atlantic caused by reduced Labrador Sea surface heat loss - Alan D. Fox; Patricia Handmann; Christina Schmidt; Neil Fraser; Siren Rühs; Alejandra Sanchez-Franks; Torge Martin; Marilena Oltmanns; Clare Johnson; Willi Rath; N. Penny Holliday; Arne Biastoch; et al. (Ocean Science, 2022)
Observations of the eastern subpolar North Atlantic in the 2010s show exceptional freshening and cooling of the upper ocean, peaking in 2016 with the lowest salinities recorded for 120 years. Published theories for the mechanisms driving the freshening include: reduced transport of saltier, warmer surface waters northwards from the subtropics associated with reduced meridional overturning; shifts in the pathways of fresher, cooler surface water from the Labrador Sea driven by changing patterns of wind stress; and the eastward expansion of the subpolar gyre. Using output from a high-resolution hindcast model simulation, we propose that the primary cause of the exceptional freshening and cooling is reduced surface heat loss in the Labrador Sea. Tracking virtual fluid particles in the model backwards from the eastern subpolar North Atlantic between 1990 and 2020 shows the major cause of the freshening and cooling to be an increased outflow of relatively fresh and cold surface waters from the Labrador Sea; with a minor contribution from reduced transport of warmer, saltier surface water northward from the subtropics. The cooling, but not the freshening, produced by these changing proportions of waters of subpolar and subtropical origin is mitigated by reduced along-track heat loss to the atmosphere in the North Atlantic Current. We analyse modelled boundary exchanges and water mass transformation in the Labrador Sea to show that since 2000, while inflows of lighter surface waters remain steady, the increasing output of these waters is due to reduced surface heat loss in the Labrador Sea beginning in the early 2000s. Tracking particles further upstream reveals that the primary source of the increased volume of lighter water transported out of the Labrador Sea is increased recirculation of water, and therefore longer residence times, in the upper 500–1000 m of the subpolar gyre.

Effect of Grain-Size Distribution on Temporal Evolution of Interfacial Area during Two-phase Flow in Porous Media - Fizza Zahid; Jeffrey A. Cunningham (Transport in Porous Media, 2022)

Mitogenomics reveals low variation within a trigeneric complex of black corals from the North Pacific Ocean - Yessenia M. Bledsoe-Becerra; Iesha S. Whittaker; Jeremy Horowitz; Katherine Medina Naranjo; Jicayla Johnson-Rosemond; Kristen H. Mullins; Karena M. Cunningham; Suchir Shetty; Samuel N. Messinides; Melinda S. Behney; Jessica A. Fehsal; Ashley N. Watson; et al. (Organisms Diversity & Evolution, 2022)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Drivers and physical processes of drought events over the State of São Paulo, Brazil - Abayomi A. Abatan; Simon F. B. Tett; Buwen Dong; Christopher Cunningham; Conrado M. Rudorff; Nicholas P. Klingaman; Rafael C. de Abreu (Climate Dynamics, 2022)
The State of São Paulo, Brazil (SSP) was impacted by severe water shortages during the intense austral summer drought of 2013/2014 and 2014/2015 (1415SD). This study seeks to understand the features and physical processes associated with these summer droughts in the context of other droughts over the region during 1961–2010. Thus, this study examines the spatio-temporal characteristics of anomalously low precipitation over SSP and the associated large-scale dynamics at seasonal timescales, using an observation-based dataset from the Climatic Research Unit (CRU) and model simulation outputs from the Met Office Hadley Centre Global Environment Model (HadGEM3-GA6 at N216 resolution). The study analyzes Historical and Natural simulations from the model to examine the role of human-induced climate forcing on droughts over SSP. Composites of large-scale fields associated with droughts are derived from ERA-20C and ERA-Interim reanalysis and the model simulations. HadGEM3-GA6 simulations capture the observed interannual variability of normalized precipitation anomalies over SSP, but with biases. Drought events over SSP are related to subsidence over the region. This is associated with reduced atmospheric moisture over the region as indicated by the analysis of the vertically integrated moisture flux convergence, which is dominated by reduced moisture flux convergence. The Historical simulations simulate the subsidence associated with droughts, but there are magnitude and location biases. The similarities between the circulation features of the severe 1415SD and other drought events over the region show that understanding of the dynamics of the past drought events over SSP could guide assessment of changes in risk of future droughts and improvements of model performance. The study highlights the merits and limitations of the HadGEM3-GA6 simulations. The model possesses the skills in simulating the large-scale atmospheric circulations modulating precipitation variability, leading to drought conditions over SSP.

COVID-19 and urban rivers: Effects of lockdown period on surface water pollution and quality- A case study of the Zarjoub River, north of Iran - Hamed Haghnazar; Jeffrey A Cunningham; Vinod Kumar; Ehsan Aghayani; Mojtaba Mehraein (Environmental Science and Pollution Research, 2022)

CropPol : A dynamic, open and global database on crop pollination - Alfonso Allen‐Perkins; Ainhoa Magrach; Matteo Dainese; Lucas A. Garibaldi; David Kleijn; Romina Rader; James R. Reilly; Rachael Winfree; Ola Lundin; Carley M. McGrady; Claire Brittain; David J. Biddinger; et al. (Ecology, 2022)
Seventy five percent of the world's food crops benefit from insect pollination. Hence, there has been increased interest in how global change drivers impact this critical ecosystem service. Because standardized data on crop pollination are rarely available, we are limited in our capacity to understand the variation in pollination benefits to crop yield, as well as to anticipate changes in this service, develop predictions, and inform management actions. Here, we present CropPol, a dynamic, open, and global database on crop pollination. It contains measurements recorded from 202 crop studies, covering 3,394 field observations, 2,552 yield measurements (i.e., berry mass, number of fruits, and fruit density [kg/ha], among others), and 47,752 insect records from 48 commercial crops distributed around the globe. CropPol comprises 32 of the 87 leading global crops and commodities that are pollinator dependent. Malus domestica is the most represented crop (32 studies), followed by Brassica napus (22 studies), Vaccinium corymbosum (13 studies), and Citrullus lanatus (12 studies). The most abundant pollinator guilds recorded are honey bees (34.22% counts), bumblebees (19.19%), flies other than Syrphidae and Bombyliidae (13.18%), other wild bees (13.13%), beetles (10.97%), Syrphidae (4.87%), and Bombyliidae (0.05%). Locations comprise 34 countries distributed among Europe (76 studies), North America (60), Latin America and the Caribbean (29), Asia (20), Oceania (10), and Africa (7). Sampling spans three decades and is concentrated on 2001–2005 (21 studies), 2006–2010 (40), 2011–2015 (88), and 2016–2020 (50). This is the most comprehensive open global data set on measurements of crop flower visitors, crop pollinators and pollination to date, and we encourage researchers to add more datasets to this database in the future. This data set is released for non‐commercial use only. Credits should be given to this paper (i.e., proper citation), and the products generated with this database should be shared under the same license terms (CC BY‐NC‐SA).

Multi-taxa spatial conservation planning reveals similar priorities between taxa and improved protected area representation with climate change - Rob Critchlow; Charles A. Cunningham; Humphrey Q. P. Crick; Nicholas A. Macgregor; Michael D. Morecroft; James W. Pearce-Higgins; Tom H. Oliver; Matthew J. Carroll; Colin M. Beale (Biodiversity and Conservation, 2022)
Protected area (PA) networks have in the past been constructed to include all major habitats, but have often been developed through consideration of only a few indicator taxa or across restricted areas, and rarely account for global climate change. Systematic conservation planning (SCP) aims to improve the efficiency of biodiversity conservation, particularly when addressing internationally agreed protection targets. We apply SCP in Great Britain (GB) using the widest taxonomic coverage to date (4,447 species), compare spatial prioritisation results across 18 taxa and use projected future (2080) distributions to assess the potential impact of climate change on PA network effectiveness. Priority conservation areas were similar among multiple taxa, despite considerable differences in spatial species richness patterns; thus systematic prioritisations based on indicator taxa for which data are widely available are still useful for conservation planning. We found that increasing the number of protected hectads by 2% (to reach the 2020 17% Aichi target) could have a disproportionate positive effect on species protected, with an increase of up to 17% for some taxa. The PA network in GB currently under-represents priority species but, if the potential future distributions under climate change are realised, the proportion of species distributions protected by the current PA network may increase, because many PAs are in northern and higher altitude areas. Optimal locations for new PAs are particularly concentrated in southern and upland areas of GB. This application of SCP shows how a small addition to an existing PA network could have disproportionate benefits for species conservation.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Testing a global standard for quantifying species recovery and assessing conservation impact - Molly K. Grace; H. Resit Akçakaya; Elizabeth L. Bennett; Thomas M. Brooks; Anna Heath; Simon Hedges; Craig Hilton‐Taylor; Michael Hoffmann; Axel Hochkirch; Richard Jenkins; David A. Keith; Barney Long; et al. (Conservation Biology, 2021)
Recognizing the imperative to evaluate species recovery and conservation impact, in 2012 the International Union for Conservation of Nature (IUCN) called for development of a “Green List of Species” (now the IUCN Green Status of Species). A draft Green Status framework for assessing species’ progress toward recovery, published in 2018, proposed 2 separate but interlinked components: a standardized method (i.e., measurement against benchmarks of species’ viability, functionality, and preimpact distribution) to determine current species recovery status (herein species recovery score ) and application of that method to estimate past and potential future impacts of conservation based on 4 metrics ( conservation legacy, conservation dependence , conservation gain , and recovery potential ). We tested the framework with 181 species representing diverse taxa, life histories, biomes, and IUCN Red List categories (extinction risk). Based on the observed distribution of species’ recovery scores, we propose the following species recovery categories : fully recovered, slightly depleted, moderately depleted, largely depleted, critically depleted, extinct in the wild, and indeterminate. Fifty‐nine percent of tested species were considered largely or critically depleted. Although there was a negative relationship between extinction risk and species recovery score, variation was considerable. Some species in lower risk categories were assessed as farther from recovery than those at higher risk. This emphasizes that species recovery is conceptually different from extinction risk and reinforces the utility of the IUCN Green Status of Species to more fully understand species conservation status. Although extinction risk did not predict conservation legacy, conservation dependence, or conservation gain, it was positively correlated with recovery potential. Only 1.7% of tested species were categorized as zero across all 4 of these conservation impact metrics , indicating that conservation has, or will, play a role in improving or maintaining species status for the vast majority of these species. Based on our results, we devised an updated assessment framework that introduces the option of using a dynamic baseline to assess future impacts of conservation over the short term to avoid misleading results which were generated in a small number of cases, and redefines short term as 10 years to better align with conservation planning. These changes are reflected in the IUCN Green Status of Species Standard.

Role of air–sea fluxes and ocean surface density in the production of deep waters in the eastern subpolar gyre of the North Atlantic - Tillys Petit; M. Susan Lozier; Simon A. Josey; Stuart A. Cunningham (Ocean Science, 2021)
Wintertime convection in the North Atlantic Ocean is a key component of the global climate as it produces dense waters at high latitudes that flow equatorward as part of the Atlantic Meridional Overturning Circulation (AMOC). Recent work has highlighted the dominant role of the Irminger and Iceland basins in the production of North Atlantic Deep Water. Dense water formation in these basins is mainly explained by buoyancy forcing that transforms surface waters to the deep waters of the AMOC lower limb. Air–sea fluxes and the ocean surface density field are both key determinants of the buoyancy-driven transformation. We analyze these contributions to the transformation in order to better understand the connection between atmospheric forcing and the densification of surface water. More precisely, we study the impact of air–sea fluxes and the ocean surface density field on the transformation of subpolar mode water (SPMW) in the Iceland Basin, a water mass that “pre-conditions” dense water formation downstream. Analyses using 40 years of observations (1980–2019) reveal that the variance in SPMW transformation is mainly influenced by the variance in density at the ocean surface. This surface density is set by a combination of advection, wind-driven upwelling and surface fluxes. Our study shows that the latter explains ∼ 30 % of the variance in outcrop area as expressed by the surface area between the outcropped SPMW isopycnals. The key role of the surface density in SPMW transformation partly explains the unusually large SPMW transformation in winter 2014–2015 over the Iceland Basin.

Smoke on the Water: Comparative Assessment of Combined Thermal Shock Treatments for Control of Invasive Asian Clam, Corbicula fluminea - Neil E. Coughlan; Ross N. Cuthbert; Eoghan M. Cunningham; Stephen Potts; Diarmuid McSweeney; Gina Y. W. Vong; Emma Healey; Kate Crane; Joe M. Caffrey; Frances E. Lucy; Eithne Davis; Jaimie T. A. Dick (Environmental Management, 2021)
Suppression of established populations of invasive alien species can be a complex and expensive process, which is frequently unsuccessful. The Asian clam, Corbicula fluminea (Müller, 1774), is considered a high impact invader that can adversely alter freshwater ecosystems and decrease their socioeconomic value. To date, C. fluminea continues to spread and persist within freshwater environments worldwide, despite repeated management attempts to prevent dispersal and suppress established populations. As extensive C. fluminea beds can often become exposed during low-water conditions, the direct application of hot or cold thermal shock treatments has been proposed as suitable mechanism for their control. Further, mechanical substrate disturbance may enhance the efficacy of thermal shock treatments by facilitating exposures to multiple layers of buried clams. In the present study, we advanced these methods by assessing combined applications of both hot and cold thermal shock treatments for control of C. fluminea , using steam spray (≥100 °C; 350 kPa), low- or high-intensity open-flame burns (~1000 °C) and dry ice (−78 °C). In a direct comparison of raking combined with hot thermal shock applications, both steam and high-intensity open-flame treatments tended to be most effective, especially following multiple applications. In addition, when hot thermal treatments are followed by a final cold shock (i.e. dry ice), steam treatments tended to be most effective. Further, when dry ice was applied either alone or prior to an application of a hot shock treatment, substantial if not complete C. fluminea mortality was observed. Overall, this study demonstrated that combined applications of hot and cold thermal shock treatments, applied following the disruption of the substrate, can substantially increase C. fluminea mortality compared to separate hot or cold treatments.

Ordovician volcanic rocks record rifting, Variscan metamorphism and gold mineralization processes (Truchas Syncline, NW Iberia, Spain) - L. González-Menéndez; F. Gómez-Fernández; J. K. Cunningham; S. Menéndez; P. Caldevilla; G. Gallastegui; A. Cuesta (Journal of Iberian Geology, 2021)

Why disease ecology needs life‐history theory: a host perspective - Andrés Valenzuela‐Sánchez; Mark Q. Wilber; Stefano Canessa; Leonardo D. Bacigalupe; Erin Muths; Benedikt R. Schmidt; Andrew A. Cunningham; Arpat Ozgul; Pieter T.J. Johnson; Hugo Cayuela (Ecology Letters, 2021)
When facing an emerging infectious disease of conservation concern, we often have little information on the nature of the host‐parasite interaction to inform management decisions. However, it is becoming increasingly clear that the life‐history strategies of host species can be predictive of individual‐ and population‐level responses to infectious disease, even without detailed knowledge on the specifics of the host‐parasite interaction. Here, we argue that a deeper integration of life‐history theory into disease ecology is timely and necessary to improve our capacity to understand, predict and mitigate the impact of endemic and emerging infectious diseases in wild populations. Using wild vertebrates as an example, we show that host life‐history characteristics influence host responses to parasitism at different levels of organisation, from individuals to communities. We also highlight knowledge gaps and future directions for the study of life‐history and host responses to parasitism. We conclude by illustrating how this theoretical insight can inform the monitoring and control of infectious diseases in wildlife.

Morphine and ethanol pretreatment effects on expression and extinction of ethanol-induced conditioned place preference and aversion in mice - Christopher L. Cunningham; Lee Bakner; Lindsey M. Schuette; Emily A. Young (Psychopharmacology, 2021)

Marker associations for fusiform rust resistance in a clonal population of loblolly pine (Pinus taeda, L.) - W. Patrick Cumbie; Dudley A. Huber; Victor C. Steel; William Rottmann; Christina Cannistra; Les Pearson; Michael Cunningham (Tree Genetics & Genomes, 2020)

Steam and Flame Applications as Novel Methods of Population Control for Invasive Asian Clam (Corbicula fluminea) and Zebra Mussel (Dreissena polymorpha) - Neil E. Coughlan; Eoghan M. Cunningham; Stephen Potts; Diarmuid McSweeney; Emma Healey; Jaimie T. A. Dick; Gina Y. W. Vong; Kate Crane; Joe M. Caffrey; Frances E. Lucy; Eithne Davis; Ross N. Cuthbert (Environmental Management, 2020)
Control strategies for established populations of invasive alien species can be costly and complex endeavours, which are frequently unsuccessful. Therefore, rapid-reaction techniques that are capable of maximising efficacy whilst minimising environmental damage are urgently required. The Asian clam ( Corbicula fluminea Müller, 1774), and the zebra mussel ( Dreissena polymorpha Pallas, 1771), are invaders capable of adversely affecting the functioning and biodiversity of freshwater ecosystems. Despite efforts to implement substantial population-control measures, both species continue to spread and persist within freshwater environments. As bivalve beds often become exposed during low-water conditions, this study examined the efficacy of steam-spray (≥100 °C, 350 kPa) and open-flame burn treatments (~1000 °C) to kill exposed individuals. Direct steam exposure lasting for 5 min caused 100% mortality of C. fluminea buried at a depth of 3 cm. Further, combined rake and thermal shock treatments, whereby the substrate is disturbed between each application of either a steam or open flame, caused 100% mortality of C. fluminea specimens residing within a 4-cm deep substrate patch, following three consecutive treatment applications. However, deeper 8-cm patches and water-saturated substrate reduced maximum bivalve species mortality rates to 77% and 70%, respectively. Finally, 100% of D. polymorpha specimens were killed following exposure to steam and open-flame treatments lasting for 30 s and 5 s, respectively. Overall, our results confirm the efficacy of thermal shock treatments as a potential tool for substantial control of low-water-exposed bivalves. Although promising, our results require validation through upscaling to field application, with consideration of other substrate types, increased substrate depth, greater bivalve densities, non-target and long-term treatment effects.

Estimates of Blood Lead Levels (BLLs) for Children in Coastal Madagascar: Accounting for Dietary Uptake of Lead (Pb) - D. Brad Akers; Adaline Buerck; Michael F. MacCarthy; Jeffrey A. Cunningham; James R. Mihelcic (Exposure and Health, 2020)

Watershed‐scale climate influences productivity of Chinook salmon populations across southcentral Alaska - Leslie A. Jones; Erik R. Schoen; Rebecca Shaftel; Curry J. Cunningham; Sue Mauger; Daniel J. Rinella; Adam St. Saviour (Global Change Biology, 2020)
The ecosystems supporting Pacific salmon ( Oncorhynchus spp.) are changing rapidly as a result of climate change and habitat alteration. Understanding how—and how consistently—salmon populations respond to changes at regional and watershed scales has major implications for fisheries management and habitat conservation. Chinook salmon ( O. tshawytscha ) populations across Alaska have declined over the past decade, resulting in fisheries closures and prolonged impacts to local communities. These declines are associated with large‐scale climate drivers, but uncertainty remains about the role of local conditions (e.g., precipitation, streamflow, and stream temperature) that vary among the watersheds where salmon spawn and rear. We estimated the effects of these and other environmental indicators on the productivity of 15 Chinook salmon populations in the Cook Inlet basin, southcentral Alaska, using a hierarchical Bayesian stock‐recruitment model. Salmon spawning during 2003–2007 produced 57% fewer recruits than the previous long‐term average, leading to declines in adult returns beginning in 2008. These declines were explained in part by density dependence, with reduced population productivity following years of high spawning abundance. Across all populations, productivity declined with increased precipitation during the fall spawning and early incubation period and increased with above‐average precipitation during juvenile rearing. Above‐average stream temperatures during spawning and rearing had variable effects, with negative relationships in many warmer streams and positive relationships in some colder streams. Productivity was also associated with regional indices of streamflow and ocean conditions, with high variability among populations. The cumulative effects of adverse conditions in freshwater, including high spawning abundance, heavy fall rains, and hot, dry summers may have contributed to the recent population declines across the region. Identifying both coherent and differential responses to environmental change underscores the importance of targeted, watershed‐specific monitoring and conservation efforts for maintaining resilient salmon runs in a warming world.

Genetic assignment, diversity, and divergence of naturalised Acacia saligna (Fabaceae) in Tigray, Ethiopia - M. A. Millar; K. Mezgebe; N. Hagazi; P. Cunningham; M. Byrne (Tree Genetics & Genomes, 2020)

A genome-wide association study implicates the BMP7 locus as a risk factor for nonsyndromic metopic craniosynostosis - Cristina M. Justice; Araceli Cuellar; Krithi Bala; Jeremy A. Sabourin; Michael L. Cunningham; Karen Crawford; Julie M. Phipps; Yan Zhou; Deirdre Cilliers; Jo C. Byren; David Johnson; Steven A. Wall; et al. (Human Genetics, 2020)

Driven by speculation, not by impact – the effects of plastic on fish species - Eoghan M. Cunningham; Konstadinos Kiriakoulakis; Jaimie T. A. Dick; Louise Kregting; Pia Schuchert; Julia D. Sigwart (Journal of Fish Biology, 2020)

High temperatures are associated with substantial reductions in breeding success and offspring quality in an arid-zone bird - T. M. F. N. van de Ven; A. E. McKechnie; S. Er; S. J. Cunningham (Oecologia, 2020)

Residual vitellus and energetic state of wolf spiderlings Pardosa saltans after emergence from egg-sac until first predation - A. Laino; M. Cunningham; F. Garcia; M. Trabalon (Journal of Comparative Physiology B, 2020)

Better off dead: assessment of aquatic disinfectants and thermal shock treatments to prevent the spread of invasive freshwater bivalves - Neil E. Coughlan; Stephanie J. Bradbeer; Ross N. Cuthbert; Eoghan M. Cunningham; Kate Crane; Stephen Potts; Joe M. Caffrey; Frances E. Lucy; Alison M. Dunn; Eithne Davis; Trevor Renals; Claire Quinn; et al. (Wetlands Ecology and Management, 2020)
Biosecurity protocols designed to prevent further spread of invasive alien species have become a key component of invader management strategies. Yet, the species-specific efficacy of many biosecurity treatments are frequently unclear or unknown. Invasive quagga, Dreissena bugensis , and zebra mussels, D. polymorpha , are a serious threat to freshwater ecosystems worldwide. Here, we examine the effectiveness of immersion (≤ 90 min) within 2% or 4% solutions for two commonly used disinfectants (Virasure® Aquatic and Virkon® Aquatic) to cause mortality of adult Dreissena bivalves . Further, we assessed the effectiveness of thermal treatments: steam spray (≥ 100 °C; ≤ 120 s); hot air (− 500 °C; ≤ 60 s); and dry ice exposure (− 78 °C; ≤ 300 g; 15 min). Complete mortality of D. polymorpha was observed following exposure to both disinfectants for 90 min, at both concentrations. However, high but incomplete mortality (40–90%) was recorded for D. bugensis across disinfectant treatments. For both species, complete mortality was achieved following 30 s of steam. In addition, 10 s of hot air and 15 min exposure to 300 g of dry ice can both completely killed groups of D. polymorpha . Overall, although the disinfectants did not cause complete mortality, it appears that relatively brief exposure to thermal treatments could be used to curtail the further spread of Dreissena species.

A reintroduced ecosystem engineer provides a germination niche for native plant species - Catherine E. Ross; Sue McIntyre; Philip S. Barton; Maldwyn J. Evans; Saul A. Cunningham; Adrian D. Manning (Biodiversity and Conservation, 2020)

Juggling a “junk-food” diet: responses of an urban bird to fluctuating anthropogenic-food availability - M. Stofberg; S.J. Cunningham; P. Sumasgutner; A. Amar (Urban Ecosystems, 2019)

Mutations in sorghum SBEIIb and SSIIa affect alkali spreading value, starch composition, thermal properties and flour viscosity - Stefanie Griebel; Richard P. Westerman; Adedayo Adeyanju; Charles Addo-Quaye; Bruce A. Craig; Clifford F. Weil; Suzanne M. Cunningham; Bhavesh Patel; Osvaldo H. Campanella; Mitchell R. Tuinstra (Theoretical and Applied Genetics, 2019)
Key message Seven novel alleles of SBEIIb and one allele of SSIIa co-segregated with the ASV phenotype and contributed to distinct starch quality traits important for food-processing applications. Abstract Sorghum is an important food crop for millions of people in Africa and Asia. Whole-genome re-sequencing of sorghum EMS mutants exhibiting an alkali spreading value (ASV) phenotype revealed candidate SNPs in Sobic.004G163700 and Sobic.010G093400 . Comparative genomics identified Sobic.010G093400 as a starch synthase IIa and Sobic.004G163700 as a starch branching enzyme IIb . Segregation analyses showed that mutations in Sobic.010G093400 or Sobic.004G163700 co-segregated with the ASV phenotype. Mutants in SSIIa exhibited no change in amylose content but expressed lower final viscosity and lower starch gelatinization temperature (GT) than starches from non-mutant plants. The sbeIIb mutants exhibited significantly higher amylose levels and starch GT and lower viscosity compared to non-mutant starches and ssIIa mutants. Mutations in SBEIIb had a dosage-dependent effect on amylose content. Double mutants of sbeIIb and ssIIa resembled their sbeIIb parent in amylose content, starch thermal properties and viscosity profiles. These variants will provide opportunities to produce sorghum varieties with modified starch end-use qualities important for the beer brewing and baking industries and specialty foods for humans with diabetes.

The costs of keeping cool: behavioural trade-offs between foraging and thermoregulation are associated with significant mass losses in an arid-zone bird - T. M. F. N. van de Ven; A. E. McKechnie; S. J. Cunningham (Oecologia, 2019)

Demodicosis in a captive African straw-coloured fruit bat (Eidolon helvum) - Carlo Bianco; Kate S. Baker; Luca Pazzini; Alessandra Cafiso; Richard D. Suu-Ire; Andrew A. Cunningham; James L. N. Wood; Alejandro Nuñez (Experimental and Applied Acarology, 2019)

Vitellogenesis in spiders: first analysis of protein changes in different reproductive stages of Polybetes pythagoricus - S. Romero; A. Laino; F. Arrighetti; C. F. García; M. Cunningham (Journal of Comparative Physiology B, 2019)

Effects of historic and projected climate change on the range and impacts of an emerging wildlife disease - Stephen J. Price; William T. M. Leung; Christopher J. Owen; Robert Puschendorf; Chris Sergeant; Andrew A. Cunningham; Francois Balloux; Trenton W. J. Garner; Richard A. Nichols (Global Change Biology, 2019)
The global trend of increasing environmental temperatures is often predicted to result in more severe disease epidemics. However, unambiguous evidence that temperature is a driver of epidemics is largely lacking, because it is demanding to demonstrate its role among the complex interactions between hosts, pathogens, and their shared environment. Here, we apply a three‐pronged approach to understand the effects of temperature on ranavirus epidemics in UK common frogs, combining in vitro, in vivo, and field studies. Each approach suggests that higher temperatures drive increasing severity of epidemics. In wild populations, ranavirosis incidents were more frequent and more severe at higher temperatures, and their frequency increased through a period of historic warming in the 1990s. Laboratory experiments using cell culture and whole animal models showed that higher temperature increased ranavirus propagation, disease incidence, and mortality rate. These results, combined with climate projections, predict severe ranavirosis outbreaks will occur over wider areas and an extended season, possibly affecting larval recruitment. Since ranaviruses affect a variety of ectothermic hosts (amphibians, reptiles, and fish), wider ecological damage could occur. Our three complementary lines of evidence present a clear case for direct environmental modulation of these epidemics and suggest management options to protect species from disease.

Sublethal effects of natural parasitism act through maternal, but not paternal, reproductive success in a wild population - Olivia Hicks; Jonathan A. Green; Francis Daunt; Emma J. A. Cunningham; Mark Newell; Adam Butler; Sarah J. Burthe (Ecology, 2019)
Parasites are a major component of all animal populations. Males and females often differ in their levels of parasite prevalence, potentially leading to sex differences in the impact of parasitism on fitness, with important implications for the evolution of parasite and host traits including resistance, tolerance, and virulence. However, quantitative measures of the impact of parasitism under free‐living conditions are extremely rare, as they require detailed host demographic data with measures of parasite burden over time. Here, we use endoscopy for direct quantification of natural‐parasite burdens and relate these to reproductive success over 7 yr in a wild population of seabirds. Contrary to predictions, only female burdens were associated with negative impacts of parasitism on breeding success, despite males having significantly higher burdens. Female reproductive success declined by 30% across the range of natural parasite burdens. These effects persisted when accounting for interannual population differences in breeding success. Our results provide quantitative estimates of profound sub‐lethal effects of parasitism on the population. Importantly, they highlight how parasites act unpredictably to shape ecological and evolutionary processes in different components of the same population, with implications for demography and selection on host and parasite traits.

Modeling the Effect of TNF-α upon Drug-Induced Toxicity in Human, Tissue-Engineered Myobundles - Brittany N. J. Davis; Jeffrey W. Santoso; Michaela J. Walker; Catherine E. Oliver; Michael M. Cunningham; Christian A. Boehm; Danielle Dawes; Samantha L. Lasater; Kim Huffman; William E. Kraus; George A. Truskey (Annals of Biomedical Engineering, 2019)

Atlantic Meridional Overturning Circulation: Observed Transport and Variability - Eleanor Frajka-Williams; Isabelle J. Ansorge; Johanna Baehr; Harry L. Bryden; Maria Paz Chidichimo; Stuart A. Cunningham; Gokhan Danabasoglu; Shenfu Dong; Kathleen A. Donohue; Shane Elipot; Patrick Heimbach; N. Penny Holliday; et al. (Frontiers in Marine Science, 2019)

Real-Time Monitoring with a Tablet App Improves Implementation of Treatments to Enhance Forest Structural Diversity - Colin T Maher; Emily Oja; Abigail Marshall; Matthew Cunningham; Lucas Townsend; Graham Worley-Hood; Luke Ruffner Robinson; Taylor Margot; Drew Lyons; Stuart Fety; Eryn E Schneider; Sean M A Jeronimo; et al. (Journal of Forestry, 2019)

Field-scale modeling of microbially induced calcite precipitation - A. B. Cunningham; H. Class; A. Ebigbo; R. Gerlach; A. J. Phillips; J. Hommel (Computational Geosciences, 2019)

Pharmaceutical Development of AAV-Based Gene Therapy Products for the Eye - Gerard A. Rodrigues; Evgenyi Shalaev; Thomas K. Karami; James Cunningham; Nigel K. H. Slater; Hongwen M. Rivers (Pharmaceutical Research, 2019)
A resurgence of interest and investment in the field of gene therapy, driven in large part by advances in viral vector technology, has recently culminated in United States Food and Drug Administration approval of the first gene therapy product targeting a disease caused by mutations in a single gene. This product, LUXTURNA™ (voretigene neparvovec-rzyl; Spark Therapeutics, Inc., Philadelphia, PA), delivers a normal copy of the RPE65 gene to retinal cells for the treatment of biallelic RPE65 mutation–associated retinal dystrophy, a blinding disease. Many additional gene therapy programs targeting both inherited retinal diseases and other ocular diseases are in development, owing to an improved understanding of the genetic basis of ocular disease and the unique properties of the ocular compartment that make it amenable to local gene therapy. Here we review the growing body of literature that describes both the design and development of ocular gene therapy products, with a particular emphasis on target and vector selection, and chemistry, manufacturing, and controls.

Experimental habitat fragmentation disrupts nematode infections in Australian skinks - Julian Resasco; Matthew E. Bitters; Saul A. Cunningham; Hugh I. Jones; Valerie J. McKenzie; Kendi F. Davies (Ecology, 2019)
Habitat conversion and fragmentation threaten biodiversity and disrupt species interactions. While parasites are recognized as ecologically important, the impacts of fragmentation on parasitism are poorly understood relative to other species interactions. This lack of understanding is in part due to confounding landscape factors that accompany fragmentation. Fragmentation experiments provide the opportunity to fill this knowledge gap by mechanistically testing how fragmentation affects parasitism while controlling landscape factors. In a large‐scale, long‐term experiment, we asked how fragmentation affects a host–parasite interaction between a skink and a parasitic nematode, which is trophically transmitted via a terrestrial amphipod intermediate host. We expected that previously observed amphipod declines resulting from fragmentation would result in decreased transmission of nematodes to skinks. In agreement, we found that nematodes were absent among skinks in the cleared matrix and that infections in fragments were about one quarter of those in continuous forest. Amphipods found in gut contents of skinks and collected from pitfall traps mirrored this pattern. A structural equation model supported the expectation that fragmentation disrupted this interaction by altering the abundance of amphipods and suggested that other variables are likely also important in mediating this effect. These findings advance understanding of how landscape change affects parasitism.

Topical Drug Delivery to the Posterior Segment of the Eye: Addressing the Challenge of Preclinical to Clinical Translation - Gerard A. Rodrigues; David Lutz; Jie Shen; Xiaoda Yuan; Hong Shen; James Cunningham; Hongwen M. Rivers (Pharmaceutical Research, 2018)

Signals of large scale climate drivers, hatchery enhancement, and marine factors in Yukon River Chinook salmon survival revealed with a Bayesian life history model - Curry J. Cunningham; Peter A. H. Westley; Milo D. Adkison (Global Change Biology, 2018)
Understanding how species might respond to climate change involves disentangling the influence of co‐occurring environmental factors on population dynamics, and is especially problematic for migratory species like Pacific salmon that move between ecosystems. To date, debate surrounding the causes of recent declines in Yukon River Chinook salmon ( Oncorhynchus tshawytscha ) abundance has centered on whether factors in freshwater or marine environments control variation in survival, and how these populations at the northern extremity of the species range will respond to climate change. To estimate the effect of factors in marine and freshwater environments on Chinook salmon survival, we constructed a stage‐structured assessment model that incorporates the best available data, estimates incidental marine bycatch mortality in trawl fisheries, and uses Bayesian model selection methods to quantify support for alternative hypotheses. Models fitted to two index populations of Yukon River Chinook salmon indicate that processes in the nearshore and marine environments are the most important determinants of survival. Specifically, survival declines when ice leaves the Yukon River later in the spring, increases with wintertime temperature in the Bering Sea, and declines with the abundance of globally enhanced salmon species consistent with competition at sea. In addition, we found support for density‐dependent survival limitations in freshwater but not marine portions of the life cycle, increasing average survival with ocean age, and age‐specific selectivity of bycatch mortality in the Bering Sea. This study underscores the utility of flexible estimation models capable of fitting multiple data types and evaluating mortality from both natural and anthropogenic sources in multiple habitats. Overall, these analyses suggest that mortality at sea is the primary driver of population dynamics, yet under warming climate Chinook salmon populations at the northern extent of the species’ range may be expected to fare better than southern populations, but are influenced by foreign salmon production.

The accessibility and utilization of genetic testing for inherited heart rhythm disorders: a Canadian cross-sectional survey study - Thomas M. Roston; Laura Dewar; Sonia Franciosi; Julie Hathaway; Kirsten Bartels; Taylor Cunningham; Karen A. Gibbs; Sam Sheps; Zachary W. M. Laksman; Shubhayan Sanatani; Andrew D. Krahn (Journal of Community Genetics, 2018)

Embryonic and post-embryonic development inside wolf spiders’ egg sac with special emphasis on the vitellus - M. Trabalon; F. Ruhland; A. Laino; M. Cunningham; F. Garcia (Journal of Comparative Physiology B, 2018)

Frequency, duration and severity of drought in the Semiarid Northeast Brazil region - S. S. B. Brito; A. P. M. A. Cunha; C. C. Cunningham; R. C. Alvalá; J. A. Marengo; M. A. Carvalho (International Journal of Climatology, 2018)
Drought is the natural disaster that impacts the greatest number of people and produces the most significant economic losses. This work presents a quantitative assessment of drought events occurred in the Semiarid region of Northeast Brazil during 1981–2016. The purpose of this study is to provide an overview of drought intensity for the last 36 years, analysing their severity, frequency and duration, considering hydro‐meteorological and agricultural aspects. To evaluate these two aspects, the 12‐month standardized precipitation index and the vegetation health index were considered to investigate drought characteristics. The definition of drought event for both these indices was performed regarding start and end month. In this context, drought duration is considered equal to the number of months of event, drought frequency is the number of events per time period and the drought severity is the absolute value of integral area below zero. Results show that the most severe and prolonged drought occurred in 2011–2016. In a clear contrast to previous droughts in past decades, during these last 5‐years period drought were more frequent, severe and affected a larger area with significant impacts for population, as well as economical activities.

Naloxone effects on extinction of ethanol- and cocaine-induced conditioned place preference in mice - Laura Font; Christa A. Houck; Christopher L. Cunningham (Psychopharmacology, 2017)

Nested PCR for Suttonella ornithocola reveals widespread infection in British Paridae species - Gabriela Peniche; Julia Rodriguez-Ramos Fernandez; Chris Durrant; Shinto K. John; Shaheed K. Macgregor; Andrew A. Cunningham; Becki Lawson (European Journal of Wildlife Research, 2017)

Large-scale forcing of the European Slope Current and associated inflows to the North Sea - Robert Marsh; Ivan D. Haigh; Stuart A. Cunningham; Mark E. Inall; Marie Porter; Ben I. Moat (Ocean Science, 2017)
The European Slope Current provides a shelf-edge conduit for Atlantic Water, a substantial fraction of which is destined for the northern North Sea, with implications for regional hydrography and ecosystems. Drifters drogued at 50 m in the European Slope Current at the Hebridean shelf break follow a wide range of pathways, indicating highly variable Atlantic inflow to the North Sea. Slope Current pathways, timescales and transports over 1988–2007 are further quantified in an eddy-resolving ocean model hindcast. Particle trajectories calculated with model currents indicate that Slope Current water is largely recruited from the eastern subpolar North Atlantic. Observations of absolute dynamic topography and climatological density support theoretical expectations that Slope Current transport is to first order associated with meridional density gradients in the eastern subpolar gyre, which support a geostrophic inflow towards the slope. In the model hindcast, Slope Current transport variability is dominated by abrupt 25–50 % reductions of these density gradients over 1996–1998. Concurrent changes in wind forcing, expressed in terms of density gradients, act in the same sense to reduce Slope Current transport. This indicates that coordinated regional changes of buoyancy and wind forcing acted together to reduce Slope Current transport during the 1990s. Particle trajectories further show that 10–40 % of Slope Current water is destined for the northern North Sea within 6 months of passing to the west of Scotland, with a general decline in this percentage over 1988–2007. Salinities in the Slope Current correspondingly decreased, evidenced in ocean analysis data. Further to the north, in the Atlantic Water conveyed by the Slope Current through the Faroe–Shetland Channel (FSC), salinity is observed to increase over this period while declining in the hindcast. The observed trend may have broadly compensated for a decline in the Atlantic inflow, limiting salinity changes in the northern North Sea during this period. Proxies for both Slope Current transport and Atlantic inflow to the North Sea are sought in sea level height differences across the FSC and between Shetland and the Scottish mainland (Wick). Variability of Slope Current transport on a wide range of timescales, from seasonal to multi-decadal, is implicit in sea level differences between Lerwick (Shetland) and Tórshavn (Faroes), in both tide gauge records from 1957 and a longer model hindcast spanning 1958–2012. Wick–Lerwick sea level differences in tide gauge records from 1965 indicate considerable decadal variability in the Fair Isle Current transport that dominates Atlantic inflow to the northwest North Sea, while sea level differences in the hindcast are dominated by strong seasonal variability. Uncertainties in the Wick tide gauge record limit confidence in this proxy.

The effect of motor overflow on bimanual asymmetric force coordination - David A. Cunningham; Sarah M. Roelle; Didier Allexandre; Kelsey A. Potter-Baker; Vishwanath Sankarasubramanian; Jayme S. Knutson; Guang H. Yue; Andre G. Machado; Ela B. Plow (Experimental Brain Research, 2017)

Effects of past and present livestock grazing on herpetofauna in a landscape‐scale experiment - Geoffrey M. Kay; Alessio Mortelliti; Ayesha Tulloch; Philip Barton; Daniel Florance; Saul A. Cunningham; David B. Lindenmayer (Conservation Biology, 2017)
Livestock grazing is the most widespread land use on Earth and can have negative effects on biodiversity. Yet, many of the mechanisms by which grazing leads to changes in biodiversity remain unresolved. One reason is that conventional grazing studies often target broad treatments rather than specific parameters of grazing (e.g., intensity, duration, and frequency) or fail to account for historical grazing effects. We conducted a landscape‐scale replicated grazing experiment (15,000 km 2 , 97 sites) to examine the impact of past grazing management and current grazing regimes (intensity, duration, and frequency) on a community of ground‐dwelling herpetofauna (39 species). We analyzed community variables (species richness and composition) for all species and built multiseason patch‐occupancy models to predict local colonization and extinction for the 7 most abundant species. Past grazing practices did not influence community richness but did affect community composition and patch colonization and extinction for 4 of 7 species. Present grazing parameters did not influence community richness or composition, but 6 of the 7 target species were affected by at least one grazing parameter. Grazing frequency had the most consistent influence, positively affecting 3 of 7 species (increased colonization or decreased extinction). Past grazing practice affected community composition and population dynamics in some species in different ways, which suggests that conservation planners should examine the different grazing histories of an area. Species responded differently to specific current grazing practices; thus, incentive programs that apply a diversity of approaches rather than focusing on a change such as reduced grazing intensity should be considered. Based on our findings, we suggest that determining fine‐scale grazing attributes is essential for advancing grazing as a conservation strategy.

Ureaplasma parvum causes hyperammonemia in a pharmacologically immunocompromised murine model - X. Wang; K. E. Greenwood-Quaintance; M. J. Karau; D. R. Block; J. N. Mandrekar; S. A. Cunningham; J. M. Mallea; R. Patel (European Journal of Clinical Microbiology & Infectious Diseases, 2017)

Morphological, ecological and behavioural differentiation of sympatric profundal and pelagic Arctic charr (Salvelinus alpinus) in Loch Dughaill Scotland - O. E. Hooker; J. Barry; T. E. Van Leeuwen; A. Lyle; J. Newton; P. Cunningham; C. E. Adams (Hydrobiologia, 2016)

An experimental test of relatedness-based mate discrimination in a social lizard - Genevieve Bordogna; George Cunningham; Luisa J. Fitzpatrick; Ben Halliwell; Hannah E. A. MacGregor; Kirke L. Munch; Erik Wapstra; Geoffrey M. While (Behavioral Ecology and Sociobiology, 2016)

The Severity of Gliosis in Hippocampal Sclerosis Correlates with Pre-Operative Seizure Burden and Outcome After Temporal Lobectomy - Alexandra M. Johnson; Ella Sugo; Daniela Barreto; Chee-Chung Hiew; John A. Lawson; Anne M. Connolly; Ernest Somerville; Enisa Hasic; Annie ME Bye; Anne M Cunningham (Molecular Neurobiology, 2016)

Silencing porcine genes significantly reduces human-anti-pig cytotoxicity profiles: an alternative to direct complement regulation - James R. Butler; Gregory R. Martens; Jose L. Estrada; Luz M. Reyes; Joseph M. Ladowski; Cesare Galli; Andrea Perota; Conor M. Cunningham; Matthew Tector; A. Joseph Tector (Transgenic Research, 2016)

Development of a Theory-based, Sociocultural Instrument to Assess Black Maternal Intentions to Vaccinate Their Daughters Aged 9 to 12 Against HPV - Jennifer Cunningham-Erves; Laura L. Talbott; Marcia R. O’Neal; Nataliya V. Ivankova; Kenneth A. Wallston (Journal of Cancer Education, 2016)

Do Fruit Ripening Volatiles Enable Resource Specialism in Polyphagous Fruit Flies? - John Paul Cunningham; Mikael A Carlsson; Tommaso F Villa; Teun Dekker; Anthony R Clarke (Journal of Chemical Ecology, 2016)

Assessing the genetic architecture of epithelial ovarian cancer histological subtypes - Gabriel Cuellar-Partida; Yi Lu; Suzanne C. Dixon; Peter A. Fasching; Alexander Hein; Stefanie Burghaus; Matthias W. Beckmann; Diether Lambrechts; Els Van Nieuwenhuysen; Ignace Vergote; Adriaan Vanderstichele; Jennifer Anne Doherty; et al. (Human Genetics, 2016)

Ecological effects of increasing time since invasion by the exotic African olive (Olea europaea ssp. cuspidata) on leaf-litter invertebrate assemblages - Kien Q. Nguyen; Peter Cuneo; Saul A. Cunningham; Dan W. Krix; Andrea Leigh; Brad R. Murray (Biological Invasions, 2016)

Network analysis of host–virus communities in bats and rodents reveals determinants of cross‐species transmission - Angela D. Luis; Thomas J. O'Shea; David T. S. Hayman; James L. N. Wood; Andrew A. Cunningham; Amy T. Gilbert; James N. Mills; Colleen T. Webb (Ecology Letters, 2015)
Bats are natural reservoirs of several important emerging viruses. Cross‐species transmission appears to be quite common among bats, which may contribute to their unique reservoir potential. Therefore, understanding the importance of bats as reservoirs requires examining them in a community context rather than concentrating on individual species. Here, we use a network approach to identify ecological and biological correlates of cross‐species virus transmission in bats and rodents, another important host group. We show that given our current knowledge the bat viral sharing network is more connected than the rodent network, suggesting viruses may pass more easily between bat species. We identify host traits associated with important reservoir species: gregarious bats are more likely to share more viruses and bats which migrate regionally are important for spreading viruses through the network. We identify multiple communities of viral sharing within bats and rodents and highlight potential species traits that can help guide studies of novel pathogen emergence.

Virtual Electrode Recording Tool for EXtracellular potentials (VERTEX): comparing multi-electrode recordings from simulated and biological mammalian cortical tissue - Richard J. Tomsett; Matt Ainsworth; Alexander Thiele; Mehdi Sanayei; Xing Chen; Marc A. Gieselmann; Miles A. Whittington; Mark O. Cunningham; Marcus Kaiser (Brain Structure and Function, 2015)

Serosurvey of canine distemper virus and canine parvovirus in wild canids and domestic dogs at the rural interface in the Coquimbo Region, Chile - G. Acosta-Jamett; A. A. Cunningham; B. M. deC. Bronsvoort; S. Cleaveland (European Journal of Wildlife Research, 2015)

Does morphology predict trophic position and habitat use of ant species and assemblages? - H. Gibb; J. Stoklosa; D. I. Warton; A. M. Brown; N. R. Andrew; S. A. Cunningham (Oecologia, 2015)

Candidate locus analysis of the TERT–CLPTM1L cancer risk region on chromosome 5p15 identifies multiple independent variants associated with endometrial cancer risk - Luis G. Carvajal-Carmona; Tracy A. O’Mara; Jodie N. Painter; Felicity A. Lose; Joe Dennis; Kyriaki Michailidou; Jonathan P. Tyrer; Shahana Ahmed; Kaltin Ferguson; Catherine S. Healey; Karen Pooley; Jonathan Beesley; et al. (Human Genetics, 2015)

Towards climate-resilient restoration in mesic eucalypt woodlands: characterizing topsoil biophysical condition in different degradation states - Suzanne M. Prober; Jacqui Stol; Melissa Piper; V.V.S.R. Gupta; Saul A. Cunningham (Plant and Soil, 2014)

Genome-wide association study of subtype-specific epithelial ovarian cancer risk alleles using pooled DNA - Madalene A. Earp; Linda E. Kelemen; Anthony M. Magliocco; Kenneth D. Swenerton; Georgia Chenevix-Trench; Yi Lu; Alexander Hein; Arif B. Ekici; Matthias W. Beckmann; Peter A. Fasching; Diether Lambrechts; Evelyn Despierre; et al. (Human Genetics, 2014)

Low Back Pain Among Irish Farmers - A. Osborne; C. Blake; D. Meredith; J. McNamara; J. Phelan; C. Cunningham (Journal of Agromedicine, 2014)

Psittacine beak and feather disease in a free-living ring-necked parakeet (Psittacula krameri) in Great Britain - Ricardo C. C. Sa; Andrew A. Cunningham; Mark P. Dagleish; Nick Wheelhouse; Ann Pocknell; Nicole Borel; Hannah L. Peck; Becki Lawson (European Journal of Wildlife Research, 2014)

Observed decline of the Atlantic meridional overturning circulation 2004–2012 - D. A. Smeed; G. D. McCarthy; S. A. Cunningham; E. Frajka-Williams; D. Rayner; W. E. Johns; C. S. Meinen; M. O. Baringer; B. I. Moat; A. Duchez; H. L. Bryden (Ocean Science, 2014)
The Atlantic meridional overturning circulation (AMOC) has been observed continuously at 26° N since April 2004. The AMOC and its component parts are monitored by combining a transatlantic array of moored instruments with submarine-cable-based measurements of the Gulf Stream and satellite derived Ekman transport. The time series has recently been extended to October 2012 and the results show a downward trend since 2004. From April 2008 to March 2012, the AMOC was an average of 2.7 Sv (1 Sv = 106 m3 s−1) weaker than in the first four years of observation (95% confidence that the reduction is 0.3 Sv or more). Ekman transport reduced by about 0.2 Sv and the Gulf Stream by 0.5 Sv but most of the change (2.0 Sv) is due to the mid-ocean geostrophic flow. The change of the mid-ocean geostrophic flow represents a strengthening of the southward flow above the thermocline. The increased southward flow of warm waters is balanced by a decrease in the southward flow of lower North Atlantic deep water below 3000 m. The transport of lower North Atlantic deep water slowed by 7% per year (95% confidence that the rate of slowing is greater than 2.5% per year).

Grassland area determines beetle assemblage dissimilarity from surrounding floodplain forest - Philip S. Barton; Matthew J. Colloff; Kimberi R. Pullen; Saul A. Cunningham (Journal of Insect Conservation, 2013)

The interaction between a drying climate and land use affects forest structure and above‐ground carbon storage - Joanne M. Bennett; Shaun C. Cunningham; Christine A. Connelly; Rohan H. Clarke; James R. Thomson; Ralph Mac Nally (Global Ecology and Biogeography, 2013)
Aim Climate change has been linked to negative effects on vegetation, including drought‐induced dieback. Large‐scale dieback not only leads to considerable carbon emissions but often leads to loss of ecological resources. We investigated whether, and how, the structure, composition and carbon content changed over a period of extended drought (the ‘ B ig D ry’) in a much‐modified forest ecosystem. We explored whether landscape configuration, management practice or soil type influenced vegetation change. Location The B ox‐ I ronbark forests of south‐eastern A ustralia. Methods In 2010, we remeasured 120 forest transects that had first been measured in 1997 by using identical field methods. Vegetation structure and composition were quantified. We used allometric growth models to estimate the expected increase in above‐ground carbon ( AGC ) storage between 1997 and 2010; these estimates were compared with observed values. Results Forest structure was systematically different between the two periods. Canopy cover, shrub cover and litter decreased between the 1997 and 2010 surveys, whereas total basal area of dead trees, dead trees in all size classes and saplings increased between the two surveys. Climate, fragment size and their interaction were the major predictors of change in most of the measured vegetation characteristics. By comparing measured AGC in 2010 and estimates from growth models, we estimated that 5.6 ± 2.1 SE t C ha −1 may have been foregone over the B ig D ry. Main conclusions Our findings add to the evidence linking climate change to negative effects on vegetation, including mortality, canopy dieback and reduced carbon sequestration. These effects may be amplified in fragmented vegetation because of greater water and heat stress. If the carbon sequestration deficit of c. 5.6 t C ha −1 were to apply across the extant Box‐Ironbark forests of V ictoria ( c . 255,400 ha), then 1.43 M t of carbon sequestration may not have occurred during the B ig D ry.

Arthropod assemblages in a focal tree species (Eucalyptus microcarpa) depends on the species mix in restoration plantings - Philip S. Barton; Matthew J. Colloff; Kimberi R. Pullen; Saul A. Cunningham (Biodiversity and Conservation, 2013)

A global quantitative synthesis of local and landscape effects on wild bee pollinators in agroecosystems - Christina M. Kennedy; Eric Lonsdorf; Maile C. Neel; Neal M. Williams; Taylor H. Ricketts; Rachael Winfree; Riccardo Bommarco; Claire Brittain; Alana L. Burley; Daniel Cariveau; Luísa G. Carvalheiro; Natacha P. Chacoff; et al. (Ecology Letters, 2013)
Bees provide essential pollination services that are potentially affected both by local farm management and the surrounding landscape. To better understand these different factors, we modelled the relative effects of landscape composition (nesting and floral resources within foraging distances), landscape configuration (patch shape, interpatch connectivity and habitat aggregation) and farm management (organic vs. conventional and local‐scale field diversity), and their interactions, on wild bee abundance and richness for 39 crop systems globally. Bee abundance and richness were higher in diversified and organic fields and in landscapes comprising more high‐quality habitats; bee richness on conventional fields with low diversity benefited most from high‐quality surrounding land cover. Landscape configuration effects were weak. Bee responses varied slightly by biome. Our synthesis reveals that pollinator persistence will depend on both the maintenance of high‐quality habitats around farms and on local management practices that may offset impacts of intensive monoculture agriculture.

The role of carrion in maintaining biodiversity and ecological processes in terrestrial ecosystems - Philip S. Barton; Saul A. Cunningham; David B. Lindenmayer; Adrian D. Manning (Oecologia, 2013)

MDMA Increases Glutamate Release and Reduces Parvalbumin-Positive GABAergic Cells in the Dorsal Hippocampus of the Rat: Role of Cyclooxygenase - John H. Anneken; Jacobi I. Cunningham; Stuart A. Collins; Bryan K. Yamamoto; Gary A. Gudelsky (Journal of Neuroimmune Pharmacology, 2013)

Performance evaluation of a new fourth-generation HIV combination antigen–antibody assay - A. Mühlbacher; H. Schennach; J. van Helden; T. Hebell; G. Pantaleo; P. Bürgisser; C. Cellerai; P. Permpikul; M. I. Rodriguez; A. Eiras; F. Alborino; P. Cunningham; et al. (Medical Microbiology and Immunology, 2013)

ABO blood group and risk of epithelial ovarian cancer within the Ovarian Cancer Association Consortium - Elizabeth M. Poole; Margaret A. Gates; Brigit A. High; Stephen J. Chanock; Daniel W. Cramer; Julie M. Cunningham; Brooke L. Fridley; Simon A. Gayther; Ellen L. Goode; Edwin S. Iversen; Jolanta Lissowska; Rachel T. Palmieri Weber; et al. (Cancer Causes & Control, 2012)

The costs of keeping cool in a warming world: implications of high temperatures for foraging, thermoregulation and body condition of an arid‐zone bird - Katherine L. du Plessis; Rowan O. Martin; Philip A. R. Hockey; Susan J. Cunningham; Amanda R. Ridley (Global Change Biology, 2012)
Recent mass mortalities of bats, birds and even humans highlight the substantial threats that rising global temperatures pose for endotherms. Although less dramatic, sublethal fitness costs of high temperatures may be considerable and result in changing population demographics. Endothermic animals exposed to high environmental temperatures can adjust their behaviour (e.g. reducing activity) or physiology (e.g. elevating rates of evaporative water loss) to maintain body temperatures within tolerable limits. The fitness consequences of these adjustments, in terms of the ability to balance water and energy budgets and therefore maintain body condition, are poorly known. We investigated the effects of daily maximum temperature on foraging and thermoregulatory behaviour as well as maintenance of body condition in a wild, habituated population of S outhern P ied B abblers T urdoides bicolor . These birds inhabit a hot, arid area of southern Africa where they commonly experience environmental temperatures exceeding optimal body temperatures. Repeated measurements of individual behaviour and body mass were taken across days varying in maximum air temperature. Contrary to expectations, foraging effort was unaffected by daily maximum temperature. Foraging efficiency , however, was lower on hotter days and this was reflected in a drop in body mass on hotter days. When maximum air temperatures exceeded 35.5 °C, individuals no longer gained sufficient weight to counter typical overnight weight loss. This reduction in foraging efficiency is likely driven, in part, by a trade‐off with the need to engage in heat‐dissipation behaviours. When we controlled for temperature, individuals that actively dissipated heat while continuing to forage experienced a dramatic decrease in their foraging efficiency. This study demonstrates the value of investigations of temperature‐dependent behaviour in the context of impacts on body condition, and suggests that increasingly high temperatures will have negative implications for the fitness of these arid‐zone birds.

Model‐guided fieldwork: practical guidelines for multidisciplinary research on wildlife ecological and epidemiological dynamics - Olivier Restif; David T. S. Hayman; Juliet R. C. Pulliam; Raina K. Plowright; Dylan B. George; Angela D. Luis; Andrew A. Cunningham; Richard A. Bowen; Anthony R. Fooks; Thomas J. O'Shea; James L. N. Wood; Colleen T. Webb (Ecology Letters, 2012)
Infectious disease ecology has recently raised its public profile beyond the scientific community due to the major threats that wildlife infections pose to biological conservation, animal welfare, human health and food security. As we start unravelling the full extent of emerging infectious diseases, there is an urgent need to facilitate multidisciplinary research in this area. Even though research in ecology has always had a strong theoretical component, cultural and technical hurdles often hamper direct collaboration between theoreticians and empiricists. Building upon our collective experience of multidisciplinary research and teaching in this area, we propose practical guidelines to help with effective integration among mathematical modelling, fieldwork and laboratory work. Modelling tools can be used at all steps of a field‐based research programme, from the formulation of working hypotheses to field study design and data analysis. We illustrate our model‐guided fieldwork framework with two case studies we have been conducting on wildlife infectious diseases: plague transmission in prairie dogs and lyssavirus dynamics in A merican and A frican bats. These demonstrate that mechanistic models, if properly integrated in research programmes, can provide a framework for holistic approaches to complex biological systems.

Atlantic transport variability at 25° N in six hydrographic sections - C. P. Atkinson; H. L. Bryden; S. A. Cunningham; B. A. King (Ocean Science, 2012)
In January and February 2010, a sixth transatlantic hydrographic section was completed across 25° N, extending the hydrographic record at this latitude to over half a century. In combination with continuous transport measurements made since 2004 at 26.5° N by the Rapid-WATCH project, we reassess transport variability in the 25° N hydrographic record. Past studies of transport variability at this latitude have assumed transport estimates from each hydrographic section to represent annual average conditions. In this study the uncertainty in this assumption is assessed through use of Rapid-WATCH observations to quantify sub-seasonal and seasonal transport variability. Whilst in the upper-ocean no significant interannual or decadal transport variability are identified in the hydrographic record, in the deep ocean transport variability in both depth and potential temperature classes suggests some interannual or decadal variability may have occurred. This is particularly striking in the lower North Atlantic Deep Water where southward transports prior to 1998 were greater than recent transports by several Sverdrups. Whilst a cooling and freshening of Denmark Straits Overflow Water has occurred which is coincident with these transport changes, these water mass changes appear to be density compensated. Transport changes are the result of changing velocity shear in the vicinity of the Deep Western Boundary Current.

Effects of exotic grass invasion on spatial heterogeneity in the ground-layer of grassy woodlands - Elizabeth A. Lindsay; Saul A. Cunningham (Biological Invasions, 2012)

Reduction of metastasis using a non-volatile buffer - Arig Ibrahim Hashim; Heather H. Cornnell; Maria de Lourdes Coelho Ribeiro; Dominique Abrahams; Jessica Cunningham; Mark Lloyd; Gary V. Martinez; Robert A. Gatenby; Robert J. Gillies (Clinical & Experimental Metastasis, 2011)

Local and remote responses to opposite Ross Sea ice anomalies: a numerical experiment with the CPTEC/INPE AGCM - Christopher A. Cunningham; José Paulo Bonatti (Theoretical and Applied Climatology, 2011)

Analytical model for screening potential CO2 repositories - Roland T. Okwen; Mark T. Stewart; Jeffrey A. Cunningham (Computational Geosciences, 2011)

Influence of carbon sources and electron shuttles on ferric iron reduction by Cellulomonas sp. strain ES6 - Robin Gerlach; Erin K. Field; Sridhar Viamajala; Brent M. Peyton; William A. Apel; Al B. Cunningham (Biodegradation, 2011)

Morphological characteristics and ageing criteria of sand gazelle (Gazella subgutturosa marica Thomas, 1897) and their use for wildlife management - Peter Low Cunningham; Mohamed A. Sandouka; Torsten Wronski (European Journal of Wildlife Research, 2011)

Generation of Priority Research Questions to Inform Conservation Policy and Management at a National Level - MURRAY A. RUDD; KAREN F. BEAZLEY; STEVEN J. COOKE; ERICA FLEISHMAN; DANIEL E. LANE; MICHAEL B. MASCIA; ROBIN ROTH; GARY TABOR; JISELLE A. BAKKER; TERESA BELLEFONTAINE; DOMINIQUE BERTEAUX; BERNARD CANTIN; et al. (Conservation Biology, 2011)
Integrating knowledge from across the natural and social sciences is necessary to effectively address societal tradeoffs between human use of biological diversity and its preservation. Collaborative processes can change the ways decision makers think about scientific evidence, enhance levels of mutual trust and credibility, and advance the conservation policy discourse. Canada has responsibility for a large fraction of some major ecosystems, such as boreal forests, Arctic tundra, wetlands, and temperate and Arctic oceans. Stressors to biological diversity within these ecosystems arise from activities of the country's resource‐based economy, as well as external drivers of environmental change. Effective management is complicated by incongruence between ecological and political boundaries and conflicting perspectives on social and economic goals. Many knowledge gaps about stressors and their management might be reduced through targeted, timely research. We identify 40 questions that, if addressed or answered, would advance research that has a high probability of supporting development of effective policies and management strategies for species, ecosystems, and ecological processes in Canada. A total of 396 candidate questions drawn from natural and social science disciplines were contributed by individuals with diverse organizational affiliations. These were collaboratively winnowed to 40 by our team of collaborators. The questions emphasize understanding ecosystems, the effects and mitigation of climate change, coordinating governance and management efforts across multiple jurisdictions, and examining relations between conservation policy and the social and economic well‐being of Aboriginal peoples. The questions we identified provide potential links between evidence from the conservation sciences and formulation of policies for conservation and resource management. Our collaborative process of communication and engagement between scientists and decision makers for generating and prioritizing research questions at a national level could be a model for similar efforts beyond Canada.

Fine‐scale heterogeneity in beetle assemblages under co‐occurring Eucalyptus in the same subgenus - Philip S. Barton; Adrian D. Manning; Heloise Gibb; David B. Lindenmayer; Saul A. Cunningham (Journal of Biogeography, 2010)
Aim Insect biodiversity is often positively associated with habitat heterogeneity. However, this relationship depends on spatial scale, with most studies focused on differences between habitats at large scales with a variety of forest tree species. We examined fine‐scale heterogeneity in ground‐dwelling beetle assemblages under co‐occurring trees in the same subgenus: Eucalyptus melliodora A. Cunn. ex Schauer and E. blakelyi Maiden (Myrtaceae). Location Critically endangered grassy woodland near Canberra, south‐eastern Australia. Methods We used pitfall traps and Tullgren funnels to sample ground‐dwelling beetles from the litter environment under 47 trees, and examined differences in diversity and composition at spatial scales ranging from 100 to 1000 m. Results Beetle assemblages under the two tree species had distinctive differences in diversity and composition. We found that E. melliodora supported a higher richness and abundance of beetles, but had higher compositional similarity among samples. In contrast, E. blakelyi had a lower abundance and species richness of beetles, but more variability in species composition among samples. Main conclusions Our study shows that heterogeneity in litter habitat under co‐occurring and closely related eucalypt species can influence beetle assemblages at spatial scales of just hundreds of metres. The differential contribution to fine‐scale alpha and beta diversity by each eucalypt can be exploited for conservation purposes by ensuring an appropriate mix of the two species in the temperate woodlands where they co‐occur. This would help not only to maximize biodiversity at landscape scales, but also to maintain heterogeneity in species richness, trophic function and biomass at fine spatial scales.

Endotoxin-induced HIF-1α stabilisation in equine endothelial cells: synergistic action with hypoxia - A. C. Brooks; N. Menzies-Gow; S. R. Bailey; F. M. Cunningham; J. Elliott (Inflammation Research, 2010)

Characterization of microsatellite loci in the straw-colored fruit bat, Eidolon helvum (Pteropodidae) - Alison J. Peel; Stephen J. Rossiter; James L. N. Wood; Andrew A. Cunningham; David R. Sargan (Conservation Genetics Resources, 2010)

Differential RNA expression of KIR alleles - Colum McErlean; Asensio A. Gonzalez; Rodat Cunningham; Ashley Meenagh; Tanya Shovlin; Derek Middleton (Immunogenetics, 2010)

Comparison of the DNA methylation profiles of human peripheral blood cells and transformed B-lymphocytes - Yan V. Sun; Stephen T. Turner; Jennifer A. Smith; Pamela I. Hammond; Alicia Lazarus; Jodie L. Van De Rostyne; Julie M. Cunningham; Sharon L. R. Kardia (Human Genetics, 2010)

Effect of pore velocity on biodegradation of cis-dichloroethene (DCE) in column experiments - Itza Mendoza-Sanchez; Robin L. Autenrieth; Thomas J. McDonald; Jeffrey A. Cunningham (Biodegradation, 2010)

The contribution of eastern-boundary density variations to the Atlantic meridional overturning circulation at 26.5° N - M. P. Chidichimo; T. Kanzow; S. A. Cunningham; W. E. Johns; J. Marotzke (Ocean Science, 2010)
We study the contribution of eastern-boundary density variations to sub-seasonal and seasonal anomalies of the strength and vertical structure of the Atlantic Meridional Overturning Circulation (AMOC) at 26.5° N, by means of the RAPID/MOCHA mooring array between April 2004 and October 2007. The major density anomalies are found in the upper 500 m, and they are often coherent down to 1400 m. The densities have 13-day fluctuations that are apparent down to 3500 m. The two strategies for measuring eastern-boundary density – a tall offshore mooring (EB1) and an array of moorings on the continental slope (EBH) – show little correspondence in terms of amplitude, vertical structure, and frequency distribution of the resulting basin-wide integrated transport fluctuations, implying that there are significant transport contributions between EB1 and EBH. Contrary to the original planning, measurements from EB1 cannot serve as backup or replacement for EBH: density needs to be measured directly at the continental slope to compute the full-basin density gradient. Fluctuations in density at EBH generate transport variability of 2 Sv rms in the AMOC, while the overall AMOC variability is 4.8 Sv rms. There is a pronounced deep-reaching seasonal cycle in density at the eastern boundary, which is apparent between 100 m and 1400 m, with maximum positive anomalies in spring and maximum negative anomalies in autumn. These changes drive anomalous southward upper mid-ocean flow in spring, implying maximum reduction of the AMOC, and vice-versa in autumn. The amplitude of the seasonal cycle of the AMOC arising from the eastern-boundary densities is 5.2 Sv peak-to-peak, dominating the 6.7 Sv peak-to-peak seasonal cycle of the total AMOC. Our analysis suggests that the seasonal cycle in density may be forced by the strong near-coastal seasonal cycle in wind stress curl.

Factors driving pathogenicity vs. prevalence of amphibian panzootic chytridiomycosis in Iberia - Susan F. Walker; Jaime Bosch; Virgilio Gomez; Trenton W. J. Garner; Andrew A. Cunningham; Dirk S. Schmeller; Miguel Ninyerola; Daniel A. Henk; Cedric Ginestet; Christian‐Philippe Arthur; Matthew C. Fisher (Ecology Letters, 2010)
Ecology Letters (2010) 13: 372–382 Abstract Amphibian chytridiomycosis is a disease caused by the fungus Batrachochytrium dendrobatidis ( Bd ). Whether Bd is a new emerging pathogen (the novel pathogen hypothesis; NPH) or whether environmental changes are exacerbating the host‐pathogen dynamic (the endemic pathogen hypothesis; EPH) is debated. To disentangle these hypotheses we map the distribution of Bd and chytridiomycosis across the Iberian Peninsula centred on the first European outbreak site. We find that the infection‐free state is the norm across both sample sites and individuals. To analyse this dataset, we use Bayesian zero‐inflated binomial models to test whether environmental variables can account for heterogeneity in both the presence and prevalence of Bd, and heterogeneity in the occurrence of the disease, chytridiomycosis. We also search for signatures of Bd ‐spread within Iberia using genotyping. We show (1) no evidence for any relationship between the presence of Bd and environmental variables, (2) a weak relationship between environmental variables and the conditional prevalence of infection, (3) stage‐dependent heterogeneity in the infection risk, (4) a strong association between altitude and chytridiomycosis, (5) multiple Iberian genotypes and (6) recent introduction and spread of a single genotype of Bd in the Pyrenees. We conclude that the NPH is consistent with the emergence of Bd in Iberia. However, epizootic forcing of infection is tied to location and shaped by both biotic and abiotic variables. Therefore, the population‐level consequences of disease introduction are explained by EPH‐like processes. This study demonstrates the power of combining surveillance and molecular data to ascertain the drivers of new emerging infections diseases.

Does the availability of arboreal honeydew determine the prevalence of ecologically dominant ants in restored habitats? - H. Gibb; S. A. Cunningham (Insectes Sociaux, 2009)

Adjustment of the basin-scale circulation at 26° N to variations in Gulf Stream, deep western boundary current and Ekman transports as observed by the Rapid array - H. L. Bryden; A. Mujahid; S. A. Cunningham; T. Kanzow (Ocean Science, 2009)
The Rapid instrument array across the Atlantic Ocean along 26° N provides unprecedented monitoring of the basin-scale circulation. A unique feature of the Rapid array is the combination of full-depth moorings with instruments measuring temperature, salinity, pressure time series at many depths with co-located bottom pressure measurements so that dynamic pressure can be measured from surface to bottom. Bottom pressure measurements show a zonally uniform rise (and fall) of bottom pressure of 0.015 dbar on a 5 to 10 day time scale, suggesting that the Atlantic basin is filling and draining on a short time scale. After removing the zonally uniform bottom pressure fluctuations, bottom pressure variations at 4000 m depth against the western boundary compensate instantaneously for baroclinic fluctuations in the strength and structure of the deep western boundary current so there is no basin-scale mass imbalance resulting from variations in the deep western boundary current. After removing the mass compensating bottom pressure, residual bottom pressure fluctuations at the western boundary just east of the Bahamas balance variations in Gulf Stream transport. Again the compensation appears to be especially confined close to the western boundary. Thus, fluctuations in either Gulf Stream or deep western boundary current transports are compensated in a depth independent (barotropic) manner very close to the continental slope off the Bahamas. In contrast, compensation for variations in wind-driven surface Ekman transport appears to involve fluctuations in both western basin and eastern basin bottom pressures, though the bottom pressure difference fluctuations appear to be a factor of 3 too large, perhaps due to an inability to resolve small bottom pressure fluctuations after removal of larger zonal average, baroclinic, and Gulf Stream pressure components. For 4 tall moorings where time series dynamic height (geostrophic pressure) profiles can be estimated from sea surface to ocean bottom and bottom pressure can be added, there is no general correlation between surface dynamic height and bottom pressure. Dynamic height on each mooring is strongly correlated with sea surface height from satellite observations and the variability in both dynamic height and satellite sea surface height decrease sharply as the western boundary is approached.

Resource allocation in a social wasp: effects of breeding system and life cycle on reproductive decisions - ELIZABETH L. JOHNSON; TYLER W. CUNNINGHAM; SARAH M. MARRINER; JENNIFER L. KOVACS; BRENDAN G. HUNT; DIMPAL B. BHAKTA; MICHAEL A. D. GOODISMAN (Molecular Ecology, 2009)
Organisms must make important decisions on how to allocate resources to reproduction. We investigated allocation decisions in the social wasp Vespula maculifrons to understand how social insects make reproductive choices. We first determined how annual colonies apportioned resources to growth and reproduction by analysing developing brood. In contrast to expectations, colonies invested in both growth (workers) and reproduction (males) simultaneously. In addition, colonies showed evidence of producing males in pulses and reversing their reproductive choices by decreasing investment in males late in the season. This reversal is consistent with theory suggesting that colonies decrease production in males if fitness of late emerging males is low. To further investigate reproductive decisions within colonies, we determined if the male mates of multiply‐mated queens varied in their reproductive success over time. Sperm use by queens did vary over time suggesting that male success may depend on sperm clumping within the female reproductive tract. Finally, we tested if colony sex ratio conformed to expectations under kin selection theory that nestmate relatedness would positively correlate with investment in new queens if workers controlled sex allocation. Surprisingly, the proportion of queens produced by colonies was negatively correlated with nestmate relatedness, suggesting that allocation may be shaped by advantages arising from increased genetic diversity resulting from multiple mating by queens. Overall, our study suggests that the reproductive decisions of colonies are flexible and may depend both on environmental cues arising from energetic needs of the colony and genetic cues arising from mating behaviours of queens.

Whole-tree sap flow is substantially diminished by leaf herbivory - Saul A. Cunningham; Kimberi R. Pullen; Matthew J. Colloff (Oecologia, 2009)

Reference-dose place conditioning with ethanol in mice: empirical and theoretical analysis - Peter A. Groblewski; Laura S. Bax; Christopher L. Cunningham (Psychopharmacology, 2008)

Patterns in the distribution of myctophid fish in the northern Scotia Sea ecosystem - Martin A. Collins; Jose C. Xavier; Nadine M. Johnston; Anthony W. North; Peter Enderlein; Geraint A. Tarling; Claire M. Waluda; Elizabeth J. Hawker; Nathan J. Cunningham (Polar Biology, 2008)

Landscape effects on crop pollination services: are there general patterns? - Taylor H. Ricketts; James Regetz; Ingolf Steffan‐Dewenter; Saul A. Cunningham; Claire Kremen; Anne Bogdanski; Barbara Gemmill‐Herren; Sarah S. Greenleaf; Alexandra M. Klein; Margaret M. Mayfield; Lora A. Morandin; Alfred Ochieng’; et al. (Ecology Letters, 2008)
Pollination by bees and other animals increases the size, quality, or stability of harvests for 70% of leading global crops. Because native species pollinate many of these crops effectively, conserving habitats for wild pollinators within agricultural landscapes can help maintain pollination services. Using hierarchical Bayesian techniques, we synthesize the results of 23 studies – representing 16 crops on five continents – to estimate the general relationship between pollination services and distance from natural or semi‐natural habitats. We find strong exponential declines in both pollinator richness and native visitation rate. Visitation rate declines more steeply, dropping to half of its maximum at 0.6 km from natural habitat, compared to 1.5 km for richness. Evidence of general decline in fruit and seed set – variables that directly affect yields – is less clear. Visitation rate drops more steeply in tropical compared with temperate regions, and slightly more steeply for social compared with solitary bees. Tropical crops pollinated primarily by social bees may therefore be most susceptible to pollination failure from habitat loss. Quantifying these general relationships can help predict consequences of land use change on pollinator communities and crop productivity, and can inform landscape conservation efforts that balance the needs of native species and people.

Effect of soil biota on growth and allocation by Eucalyptus microcarpa - Mark Bourne; Adrienne B. Nicotra; Matthew J. Colloff; Saul A. Cunningham (Plant and Soil, 2008)

Real-time PCR assay for detection and relative quantification of Liocarcinus depurator larvae from plankton samples - Maria Pan; Alastair J. A. McBeath; Steve J. Hay; Graham J. Pierce; Carey O. Cunningham (Marine Biology, 2008)

A cDNA Microarray for Crassostrea virginica and C. gigas - Matthew J. Jenny; Robert W. Chapman; Annalaura Mancia; Yian A. Chen; David J. McKillen; Hal Trent; Paul Lang; Jean-Michel Escoubas; Evelyne Bachere; Viviane Boulo; Z. John Liu; Paul S. Gross; et al. (Marine Biotechnology, 2007)

Parasite species richness in carnivores: effects of host body mass, latitude, geographical range and population density - Patrik Lindenfors; Charles L. Nunn; Kate E. Jones; Andrew A. Cunningham; Wes Sechrest; John L. Gittleman (Global Ecology and Biogeography, 2007)
Aim Comparative studies have revealed strong links between ecological factors and the number of parasite species harboured by different hosts, but studies of different taxonomic host groups have produced inconsistent results. As a step towards understanding the general patterns of parasite species richness, we present results from a new comprehensive data base of over 7000 host–parasite combinations representing 146 species of carnivores (Mammalia: Carnivora) and 980 species of parasites. Methods We used both phylogenetic and non‐phylogenetic comparative methods while controlling for unequal sampling effort within a multivariate framework to ascertain the main determinants of parasite species richness in carnivores. Results We found that body mass, population density, geographical range size and distance from the equator are correlated with overall parasite species richness in fissiped carnivores. When parasites are classified by transmission mode, body mass and home range area are the main determinants of the richness of parasites spread by close contact between hosts, and population density, geographical range size and distance from the equator account for the diversity of parasites that are not dependent on close contact. For generalist parasites, population density, geographical range size and latitude are the primary predictors of parasite species richness. We found no significant ecological correlates for the richness of specialist or vector‐borne parasites. Main conclusions Although we found that parasite species richness increases instead of decreases with distance from the equator, other comparative patterns in carnivores support previous findings in primates, suggesting that similar ecological factors operate in both these independent evolutionary lineages.

Levels of intra-host and temporal sequence variation in a large CO1 sub-units from Anisakis simplex sensu stricto (Rudolphi 1809) (Nematoda: Anisakisdae): implications for fisheries management - M. A. Cross; C. Collins; N. Campbell; P. C. Watts; J. C. Chubb; C. O. Cunningham; E. M. C. Hatfield; K. MacKenzie (Marine Biology, 2007)

Endotoxin-induced activation of equine platelets: evidence for direct activation of p38 MAPK pathways and vasoactive mediator production - A. C. Brooks; N. J. Menzies-Gow; C. Wheeler-Jones; S. R. Bailey; F. M. Cunningham; J. Elliott (Inflammation Research, 2007)

Average body length of arboreal and aerial beetle (Coleoptera) assemblages from remnant and plantation Eucalyptus forests in southwestern Australia - Saul A. Cunningham; William Murray (Oecologia, 2007)

New Resources for Marine Genomics: Bacterial Artificial Chromosome Libraries for the Eastern and Pacific Oysters (Crassostrea virginica and C. gigas) - Charles Cunningham; Jun-ichi Hikima; Matthew J. Jenny; Robert W. Chapman; Guang-Chen Fang; Chris Saski; Mats L. Lundqvist; Rod A. Wing; Pauline M. Cupit; Paul S. Gross; Greg W. Warr; Jeff P. Tomkins (Marine Biotechnology, 2006)

Predicting Pathogen Introduction: West Nile Virus Spread to Galápagos - A. MARM KILPATRICK; PETER DASZAK; SIMON J. GOODMAN; HELMUTH ROGG; LAURA D. KRAMER; VIRNA CEDEÑO; ANDREW A. CUNNINGHAM (Conservation Biology, 2006)
Emerging infectious diseases are a key threat to conservation and public health, yet predicting and preventing their emergence is notoriously difficult. We devised a predictive model for the introduction of a zoonotic vector‐borne pathogen by considering each of the pathways by which it may be introduced to a new area and comparing the relative risk of each pathway. This framework is an adaptation of pest introduction models and estimates the number of infectious individuals arriving in a location and the duration of their infectivity. We used it to determine the most likely route for the introduction of West Nile virus to Galápagos and measures that can be taken to reduce the risk of introduction. The introduction of this highly pathogenic virus to this unique World Heritage Site could have devastating consequences, similar to those seen following introductions of pathogens into other endemic island faunas. Our model identified the transport of mosquitoes on airplanes as the highest risk for West Nile virus introduction. Pathogen dissemination through avian migration and the transportation of day‐old chickens appeared to be less important pathways. Infected humans and mosquitoes transported in sea containers, in tires, or by wind all represented much lower risk. Our risk‐assessment framework has broad applicability to other pathogens and other regions and depends only on the availability of data on the transport of goods and animals and the epidemiology of the pathogen.

Feline Immunodeficiency Virus and Puma Lentivirus in Florida panthers (Puma concolor coryi): Epidemiology and Diagnostic Issues - D. L. Miller; S. K. Taylor; D. S. Rotstein; M. B. Pough; M. C. Barr; C. A. Baldwin; M. Cunningham; M. Roelke; D. Ingram (Veterinary Research Communications, 2006)

Contribution of serotonin (5-HT) 5-HT2 receptor subtypes to the discriminative stimulus effects of cocaine in rats - Malgorzata Filip; Marcy J. Bubar; Kathryn A. Cunningham (Psychopharmacology, 2006)

Infectious pancreatic necrosis virus in Atlantic salmon, Salmo salar L., post‐smolts in the Shetland Isles, Scotland: virus identification, histopathology, immunohistochemistry and genetic comparison with Scottish mainland isolates - D A Smail; N Bain; D W Bruno; J A King; F Thompson; D J Pendrey; S Morrice; C O Cunningham (Journal of Fish Diseases, 2006)
During mid‐June 1999 peak mortalities of 11% of the total stock per week were seen at a sea cage site of Atlantic salmon, Salmo salar L., post‐smolts in the Shetland Isles, Scotland. Virus was isolated on chinook salmon embryo (CHSE) cells in a standard diagnostic test and infectious pancreatic necrosis virus (IPNV) identified by enzyme‐linked immunosorbent assay. IPNV was confirmed as serogroup A by a cell immunofluorescent antibody test using the cross‐reactive monoclonal antibody AS‐1. Four weeks after the main outbreak, virus titres in surviving moribund fish were assayed at >10 10 TCID 50 g −1 kidney. Histopathology of moribund fish was characterized by pancreatic acinar cell necrosis and a marked catarrhal enteritis of the intestinal mucosa. In the liver, necrosis, leucocytic infiltration and a generalized cell vacuolation were noted. IPNV‐specific immunostaining was demonstrated in pancreas, liver, heart, gill and kidney tissue. The nucleotide sequence of the coding region of segment A was determined from the Shetland isolate. A 1180 bp fragment of the VP2 gene of this isolate was compared with a 1979 reference isolate from mainland Scottish Atlantic salmon, La/79 and another more recent mainland isolate, 432/00. Both A2 isolates were derived from carrier fish without signs of IPN and serotyped by a plaque neutralization test. The Shetland isolate shows a different nucleotide and amino acid sequence compared with the two isolates from carrier fish. These latter isolates showed identical amino acid sequences in the fragment examined, despite the 21 years separating the isolations. Sequence comparisons with other A2 (Sp) isolates on the database confirm all three Scottish isolates are A2 (Sp).

GABA-benzodiazepine receptor function in alcohol dependence: a combined 11C-flumazenil PET and pharmacodynamic study - A. R. Lingford-Hughes; S. J. Wilson; V. J. Cunningham; A. Feeney; B. Stevenson; D. J. Brooks; D. J. Nutt (Psychopharmacology, 2005)

Phylogenetic Analysis of the DNA Polymerase Gene of a Novel Alphaherpesvirus Isolated from an Indian Gyps Vulture - Maria Cardoso; Alex Hyatt; Paul Selleck; Sue Lowther; Vibhu Prakash; Deborah Pain; Andrew A. Cunningham; David Boyle (Virus Genes, 2005)

Hydrothermal vent gastropods from the same family (Provannidae) harbour ɛ‐ and γ‐proteobacterial endosymbionts - Hidetoshi Urakawa; Nicole Dubilier; Yoshihiro Fujiwara; Dale E. Cunningham; Shigeaki Kojima; David A. Stahl (Environmental Microbiology, 2005)
Summary The discovery of new hydrothermal vent systems in the back‐arc basins of the Western Pacific revealed chemosynthesis‐based faunal communities distinct from those of other vents. These vents are dominated by two related gastropods ( Alviniconcha spp. and Ifremeria nautilei ) that harbour symbiotic bacteria in their gills. We used comparative 16S ribosomal RNA (rRNA) gene sequencing and in situ hybridization with rRNA‐targeted probes to characterize the bacterial symbionts of Alviniconcha sp. and I. nautilei from the Manus Basin in the Western Pacific. The analyses revealed that these two gastropod species, although affiliated with the same family, harbour phylogenetically distant chemosymbionts, suggesting independent origins of these endosymbioses. The I. nautilei endosymbiont clusters with sulfur‐oxidizing bacteria within the γ‐Proteobacteria, as is the case for all previously characterized endosymbionts from a wide diversity of host taxa harbouring thioautotrophic prokaryotes. In contrast, the Alviniconcha endosymbiont is affiliated with sulfur‐oxidizing bacteria within the ɛ‐Proteobacteria. These results show that bacteria from the ɛ‐Proteobacteria are also capable of forming endosymbiotic associations with marine invertebrates from chemosynthetic environments. More generally, the endosymbiotic lifestyle is now shown to be distributed throughout all recognized classes of the Proteobacteria.

Role of the serotonin 5-HT2A receptor in the hyperlocomotive and hyperthermic effects of (+)-3,4-methylenedioxymethamphetamine - David V. Herin; Shijing Liu; Thomas Ullrich; Kenner C. Rice; Kathryn A. Cunningham (Psychopharmacology, 2005)

The prevalence of escaped farmed salmon, Salmo salar L., in the River Ewe, western Scotland, with notes on their ages, weights and spawning distribution - J. R. A. BUTLER; P. D. CUNNINGHAM; K. STARR (Fisheries Management and Ecology, 2005)
The prevalence of escaped farmed Atlantic salmon, Salmo salar L., in the River Ewe, western Scotland, was assessed. After the establishment of smolt cages in the catchment and marine cages near the river mouth during 1986–1987, approximately 425 000 parr and smolts, and 122 000 growers have escaped. Between 1987 and 2001, farmed salmon occurred in the rod fishery in 13 of the 15 years, contributing at least 5.8% of the total catch, with a maximum annual frequency of 27.1%. It was estimated that P

Mitochondrial evolution and phylogeography in the hydrozoan Obelia geniculata (Cnidaria) - A. F. Govindarajan; K. M. Halanych; C. W. Cunningham (Marine Biology, 2005)

Allopregnanolone does not influence ethanol-induced conditioned place preference in DBA/2J mice - Kara I. Gabriel; Christopher L. Cunningham; Deborah A. Finn (Psychopharmacology, 2004)

Vulnerability of mouse cortical neurons to doxorubicin-induced apoptosis is strain-dependent and is correlated with mRNAs encoding Fas, Fas-Ligand, and metalloproteinases - M. Wetzel; J. Tibbitts; G. A. Rosenberg; L. A. Cunningham (Apoptosis, 2004)

Effects of dopamine D 1 - or D 2 -like receptor antagonists on the hypermotive and discriminative stimulus effects of (+)-MDMA - Marcy J. Bubar; Kami M. Pack; Paul S. Frankel; Kathryn A. Cunningham (Psychopharmacology, 2004)

Antioxidant enzyme activity and mRNA expression in the islets of Langerhans from the BB/S rat model of type 1 diabetes and an insulin-producing cell line - Louise A. Sigfrid; James M. Cunningham; Neil Beeharry; L. A. Hkan Borg; Alma L. Rosales Hernandez; Carina Carlsson; Adrian J. Bone; Irene C. Green (Journal of Molecular Medicine, 2004)

Apparatus bias and place conditioning with ethanol in mice - Christopher L. Cunningham; Nikole K. Ferree; MacKenzie A. Howard (Psychopharmacology, 2003)

Increased risk for developmental delay in Saethre-Chotzen syndrome is associated with TWIST deletions: an improved strategy for TWIST mutation screening - Juanliang Cai; Barbara K. Goodman; Ankita S. Patel; John B. Mulliken; Lionel Van Maldergem; George E. Hoganson; William A. Paznekas; Ziva Ben-Neriah; Ruth Sheffer; Michael L. Cunningham; Donna L. Daentl; Ethylin Wang Jabs (Human Genetics, 2003)

Reduced ethanol-induced conditioned taste aversion and conditioned place preference in GIRK2 null mutant mice - Katherine G. Hill; Herminia Alva; Yuri A. Blednov; Christopher L. Cunningham (Psychopharmacology, 2003)

Causes and Effects of Temporospatial Declines of Gyps Vultures in Asia - D. J. Pain; A. A. Cunningham; P. F. Donald; J. W. Duckworth; D. C. Houston; T. Katzner; J. Parry‐Jones; C. Poole; V. Prakash; P. Round; R. Timmins (Conservation Biology, 2003)

Cancer in Indigenous Australians: a review - J.R. B.K. Condon; A. Barnes; J. Cunningham (Cancer Causes & Control, 2003)

Compensation for herbivory by Cucumis sativus through increased photosynthetic capacity and efficiency - Vivien P. Thomson; Saul A. Cunningham; Marilyn C. Ball; Adrienne B. Nicotra (Oecologia, 2003)

The sodium channel blocker RS100642 reverses down-regulation of the sodium channel α-subunit Nav 1.1 expression caused by transient ischemic brain injury in rats - C. Yao; A. J. Williams; X. -C. M. Lu; R. A. Price; B. S. Cunningham; R. Berti; F. C. Tortella; J. R. Dave (Neurotoxicity Research, 2003)

Morphological and genetic evidence for vicariance and refugium in Atlantic and Gulf of Mexico populations of the hermit crab Pagurus longicarpus - Young A.; Torres C.; Mack J.; Cunningham C. (Marine Biology, 2002)

exma: an X-linked insertional mutation that disrupts forebrain and eye development - David Cunningham; Qiang Xiao; Aurobindo Chatterjee; Kathleen Sulik; Diana Juriloff; Frederick Elder; Wilbur Harrison; Gabriele Schuster; Paul A. Overbeek; Gail E. Herman (Mammalian Genome, 2002)

Conservation in a Region of Political Instability: Bwindi Impenetrable Forest, Uganda - A. Hamilton; A. Cunningham; D. Byarugaba; F. Kayanja (Conservation Biology, 2000)

Conservation in a Region of Political Instability: Bwindi Impenetrable Forest, Uganda - A. Hamilton; A. Cunningham; D. Byarugaba; F. Kayanja (Conservation Biology, 2000)
Bwindi Impenetrable is the most important forest in Uganda for conservation of biodiversity. It contains over half the world's mountain gorillas. It is surrounded by densely populated agricultural land and lies within a region of political instability. Gazetted as a forest reserve in 1932, little forest now remains outside its boundaries. Transformation of nearby communal swampland to farmland, much owned by a few individuals, shows the probable fate of Bwindi if it had not been declared a protected area. Widespread illegal logging and other activities were among reasons why the status of the forest was raised to national park in 1991. This resulted in local resentment, fed by inadequate consultation and concern about the local people's loss of access to resources. Fires were set in the forest and threats made against the gorillas. Three schemes to provide benefits from the existence of the forest to communities and involve them in park management were then instituted: agreements allowing controlled harvesting of resources in the park, receipt of some revenue from tourism, and establishment of a trust fund partly for community development. Tension between people and park has been reduced. This case demonstrates the importance of protected areas and community involvement in such circumstances. Community support is especially critical, as here, when resources available to park managers are limited and political instability endemic.

Factors affecting the presence of the cool temperate rain forest tree myrtle beech ( Nothofagus cunninghamii ) in southern Australia: integrating climatic, terrain and disturbance predictors of distribution patterns - D. B. Lindenmayer; B. G. Mackey; R. B. Cunningham; C. F. Donnelly; I. C. Mullen; M. A. McCarthy; A. M. Gill (Journal of Biogeography, 2000)
Aim This study identified the factors influencing the presence, stocking rate and basal area of the southern Australian cool temperate rain forest tree myrtle beech ( Nothofagus cunninghamii ). Location This investigation was conducted in the montane ash forests of the Central Highlands of Victoria, south‐eastern Australia. Methods The occurrence of N. cunninghamii was measured as part of field surveys of 474 sites (2844 plots) distributed widely throughout mountain ash ( Eucalyptus regnans ), alpine ash ( E. delegatensis ) and shining gum ( E. nitens ) forests. Statistical analysis was employed to examine relationships between the occurrence of N. cunninghamii and measured site attributes and interpolated and derived environmental variables. Results The presence of N. cunninghamii was significantly related to five variables: the age of the overstorey eucalypt stand, dominant species of overstorey eucalypt tree, topographic position in the landscape, slope and the estimated quantity of precipitation in the warmest quarter of the year. N. cunninghamii was more likely to occur in old growth eucalypt stands, in gullies and locations with high values for rainfall in the warmest quarter. In addition, there was an interaction between slope and dominant eucalypt tree species—in forests dominated by E. regnans , N. cunninghamii was more likely to occur on steep slopes whereas in E. nitens and E. delegatensis ‐dominated stands, N. cunninghamii was more likely to occur on flatter terrain. Statistical modelling also showed a significant positive effect of slope on both the stocking rate and basal area of the species. The stocking rate of N. cunninghamii also was significantly higher in old growth eucalypt stands. Main conclusions The study demonstrated that the patterns of distribution of N. cunninghamii may be more complex than recognized previously and it illustrated the importance of multiple factors including climatic conditions, disturbance processes (as reflected through the age of the dominant overstorey eucalypt stands) and topography. Our work also shows there can be complex interactions between age cohorts of different tree species in the same stand—in this case, the dominant overstorey eucalypts and the understorey which includes N. cunninghamii stems.

Effects of Habitat Fragmentation on the Reproductive Ecology of Four Plant Species in Mallee Woodland - Saul A. Cunningham (Conservation Biology, 2000)
Habitat fragmentation has the potential to affect plant reproduction by changing the community of pollinators and natural enemies, the neighborhood of potential mates, the availability of resources, and microclimate. I examined the effect of habitat fragmentation on reproduction of four species found in mallee woodlands of central New South Wales, Australia: Acacia brachybotrya , Senna artemisioides , Eremophila glabra , and Dianella revoluta . At six sites I surveyed plants in a reserve and in a nearby linear strip of vegetation. Two additional sites were established in a large reserve. Many effects were apparent at the extreme end of fragmentation, revealed by two‐way analysis of covariance comparing reserves and linear strips at each site. The nature of the response differed among species. Flower production was greater in most linear strip fragments for S. artemisioides and E. glabra . Fruit set efficiency was significantly greater in linear strips for S. artemisioides and significantly lower for A. brachybotrya , E. glabra , and D. revoluta . Fruit predation was lower in most linear strips for E. glabra . For A. brachybotrya , fruit predation was significantly lower in linear strips. The net effect of these changes was a significant increase in whole‐plant seed production for S. artemisioides , a significant decrease in whole‐plant seed production for A. brachybotrya and in whole‐plant fruit production for D. revoluta , and no consistent effect on whole‐plant fruit production for E. glabra . In contrast, the only pattern apparent when the effect of fragment size was considered over a range from linear strips 140,000 ha was a positive correlation between the fragment size and fruit‐set efficiency of A. brachybotrya . These results suggest that habitat fragmentation can significantly alter important reproductive functions of species, by changing both the plant's physical environment and its interactions with animals.

Enhanced anaerobic bioremediation of groundwater contaminated by fuel hydrocarbons at Seal Beach, California - Jeffrey A. Cunningham; Gary D. Hopkins; Carmen A. Lebron; Martin Reinhard (Biodegradation, 2000)

Comparative studies of piscine and amphibian iridoviruses - A. D. Hyatt; A. R. Gould; Z. Zupanovic; A. A. Cunningham; S. Hengstberger; R. J. Whittington; J. Kattenbelt; B. E. H. Coupar (Archives of Virology, 2000)

Diminished energy metabolism and enhanced apoptosis in livers of B6C3F1 mice treated with the antihepatocarcinogen rotenone - C. Wang; J. Youssef; B. Saran; P.G. Rothberg; M.L. Cunningham; A. Molteni; M. Badr (Molecular and Cellular Biochemistry, 1999)

Reply to the comment by C.S. Spirakis - C. G. Cunningham; J. D. Rasmussen; T. A. Steven; R. O. Rye; P. D. Rowley; S. B. Romberger; J. Selverstone (Mineralium Deposita, 1999)

GABA A receptors modulate ethanol-induced conditioned place preference and taste aversion in mice - J. A. Chester; Christopher L. Cunningham (Psychopharmacology, 1999)

Insulitis and mechanisms of disease resistance: studies in an animal model of insulin dependent diabetes mellitus - A. J. Bone; P. R. Hitchcock; D. J. Gwilliam; J. M. Cunningham; J. Barley (Journal of Molecular Medicine, 1999)

Sheep CD4 + αβ T cells express novel members of the T19 multigene family - Meredith A. O'Keeffe; S. A. Metcalfe; Craig P. Cunningham; I. D. Walker (Immunogenetics, 1999)

Relic permafrost structures in the Gobi of Mongolia: age and significance - Lewis A. Owen; Ben Richards; Edward J. Rhodes; W. Dickson Cunningham; Brian F. Windley; J. Badamgarav; D. Dorjnamjaa (Journal of Quaternary Science, 1998)

Extinction of a Species of Land Snail Due to Infection with a Microsporidian Parasite - Andrew A. Cunningham; Peter Daszak (Conservation Biology, 1998)
Snails of the genus Partula are highly endangered, with many species occurring solely in captivity. Captive populations experience periodic crashes, some of which have resulted in extinction. Pathologic investigations of the last individuals of a species that had undergone such a crash ( Partula turgida ) showed infection with a protozoan parasite as the cause of death. The parasite was identified as a member of the microsporidian genus Steinhausia , other members of which are known to cause mortality in aquatic pulmonate snails. We believe this is the first definitive report of an infectious disease causing the extinction of a species. Extinción de una especie de Caracol Terrestre Debido a una Infección por un Parásito Microsporidio Los caracoles del género Partula estan altamente amenazados junto con muchas especies existiendo únicamente en cautividad. Las poblaciones cautivas experimentan colapsos periódicos, algunos de los cuales han resultado en extinciones. Investigaciones patológicas de los últimos individuos de una especie que ha pasado por este tipo de colapso ( Partula turgida ) muestran infecciones de un protozoario parásito como la causa de su muerte. El parásito ha sido identificado como un miembro del género Steinhausia , otros miembros de este género han sido identificados como los causantes de mortalidades en caracoles pulmonados acuáticos. Creemos que este es un reporte definitivo de una enfermedad infecciosa causante de la extinción de una especie.

Comparison of Ceralure and Trimedlure Controlled-Release Formulations for Male Mediterranean Fruit Flies in C&C Traps - J. D. Warthen; R. T. Cunningham; B. A. Leonhardt; J. M. Cook; J. W. Avery; E. M. Harte (Journal of Chemical Ecology, 1998)

Hydrothermal uranium deposits containing molybdenum and fluorite in the Marysvale volcanic field, west-central Utah - C. G. Cunningham; J. D. Rasmussen; T. A. Steven; R. O. Rye; P. D. Rowley; S. B. Romberger; J. Selverstone (Mineralium Deposita, 1998)

The discriminative stimulus properties of cocaine: effects of microinfusion of cocaine, a 5-HT 1A agonist or antagonist, into the ventral tegmental area - R. De La Garza II; Patrick M. Callahan; K. A. Cunningham (Psychopharmacology, 1998)

(+)-ABA content and lipid deposition in interior spruce somatic embryos - Danielle Julie Carrier; Cheryl A. Bock; James E. Cunningham; David R. Cyr; David I. Dunstan (In Vitro Cellular & Developmental Biology - Plant, 1997)

The effect of light environment, leaf area, and stored carbohydrates on inflorescence production by a rain forest understory palm - Saul A. Cunningham (Oecologia, 1997)

Improved Controlled-Release Formulations for a New Trap Design for Male Mediterranean Fruit Flies: The C&C Trap - J. D. Warthen; R. T. Cunningham; B. A. Leonhardt; J. M. Cook; J. W. Avery; E. M. Harte (Journal of Chemical Ecology, 1997)

Quaternary alluvial fans in the Gobi of southern Mongolia: evidence for neotectonics and climate change - L. A. Owen; B. F. Windley; W. D. Cunningham; J. Badamgarav; D. Dorjnamjaa (Journal of Quaternary Science, 1997)

Serotonergic mechanisms involved in the discriminative stimulus, reinforcing and subjective effects of cocaine - Sharon L. Walsh; K. A. Cunningham (Psychopharmacology, 1997)

The carcinogenicity of diethylstilbestrol: structural evidence for a non-genotoxic mechanism - A. Cunningham; G. Klopman; H. S. Rosenkranz (Archives of Toxicology, 1996)

Portage: A new early-maturing, round white table potato variety - A. F. Reeves; G. A. Porter; C. E. Cunningham; R. J. Nickeson; F. E. Manzer; T. M. Work; A. A. Davis; E. S. Plissey (American Journal of Potato Research, 1995)

Integrating local plant resources and habitat management - A. B. Cunningham (Biodiversity and Conservation, 1994)

Prestile: A new round white potato variety - A. F. Reeves; G. A. Porter; C. E. Cunningham; R. J. Nickeson; F. E. Manzer; T. M. Work; A. A. Davis; E. S. Plissey (American Journal of Potato Research, 1994)

A vector-sum process produces curved aiming paths under rotated visual-motor mappings - H. A. Cunningham; I. Vardi (Biological Cybernetics, 1990)

Effects of diflubenzuron (Dimilin) on survival, molting, and behavior of juvenile fiddler crabs,Uca pugilator - Patricia A. Cunningham; Lawrence E. Myers (Archives of Environmental Contamination and Toxicology, 1987)

Campbell 14: A verticillium resistant round white potato variety - A. F. Reeves; C. E. Cunningham; R. L. Nickeson; R. V. Akeley; H. J. Murphy; F. E. Manzer; R. H. True (American Journal of Potato Research, 1985)

Sunrise: An early maturing, golden nematode resistant, round, white potato variety - A. F. Reeves; R. V. Akeley; C. E. Cunningham; H. J. Murphy; R. H. True; F. E. Manzer (American Journal of Potato Research, 1985)

Yankee Supreme: A new bruise-resistant potato variety - A. F. Reeves; R. V. Akeley; C. E. Cunningham; R. L. Nickeson; H. J. Murphy; R. H. True; F. E. Manzer (American Journal of Potato Research, 1984)

Vocal learning in White-crowned Sparrows: sensitive phase and song dialects - Michael A. Cunningham; Myron Charles Baker (Behavioral Ecology and Sociobiology, 1983)

The role of male vs male interactions in maintaining population dialect structure - Myron Charles Baker; Daniel B. Thompson; Gregory L. Sherman; Michael A. Cunningham (Behavioral Ecology and Sociobiology, 1981)

Variation in the hepatotoxic effects of carbon disulphide between different strains of rat - S. P. Tucker; D. P. Lovell; A. A. Seawright; V. J. Cunningham (Archives of Toxicology, 1980)

Chronic effects of ingested asbestos in rats - H. M. Cunningham; C. A. Moodie; G. A. Lawrence; R. D. Pontefract (Archives of Environmental Contamination and Toxicology, 1977)

Biochemical characterization of six trisomics of grain sorghum, Sorghum bicolor (L.) Moench - H. W. Suh; D. R. Goforth; Bryce A. Cunningham; G. H. Liang (Biochemical Genetics, 1977)

s of papers presented at the 50th Anniversary Meeting of The Potato Association of America and 13th National Potato Utilization Conference Perkins Inn, Riverhead, New York July 15, 16, 17, 18, 1963 - Glenn D. Boyd; Calderon Peter; Ora Smith; L. R. Mattick; John C. Campbell; R. C. Cetas; Carl O. Davis; Smith Ora; C. H. Dearborn; F. H. Drazga; R. K. Eskew; F. B. Talley; et al. (American Journal of Potato Research, 1963)

Report of Potato Utilization Committee - Paul A. Xander; Charles E. Cunningham; Robert H. Treadway (American Journal of Potato Research, 1961)

Report of the potato utilization committee - C. E. Cunningham; O. C. Turnquist; D. R. Isleib; E. J. Wheeler; R. L. Sawyer; P. A. Xander; W. C. Sparks; R. H. Treadway (American Journal of Potato Research, 1959)